Crystal form of at2r antagonist compound, salt thereof, crystal form of salt thereof, and use
Patent Information
- Application Number
- CN202610458067.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2026-04-01
- Filing Date
- 2026-04-08
- Publication Date
- 2026-10-16
AI Technical Summary
但这些药物没有针对性,治疗效果非常有限,而且有严重的副作用,包括认知改变、镇静作用、恶心以及耐受性和依赖性,远未满足临床用药需求
[0204] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention.
Smart Images

Figure CN122916987A_ABST
Abstract
Description
[0001] Priority information This application claims priority and benefits to patent applications filed with the China National Intellectual Property Administration on April 8, 2025 and April 1, 2026, with patent application numbers 2025104359863 and 2026104249815, which are incorporated herein by reference in their entirety. Technical Field
[0002] This invention relates to the pharmaceutical field, specifically to the crystal form of an AT2R antagonist, its salt, the crystal form of its salt, and its application in pharmaceuticals, specifically to (S)-3-((4-(3-(difluoromethoxy)-5-isobutyl-2-(2H-tetrazole-5-yl)phenyl)-2-methylpiperazin-1-yl)methyl)pyridazine (the compound shown in formula (I)), its salt, the crystal form of its salt, and its application in pharmaceuticals. Background Technology AT2R typically refers to angiotensin II receptor type 2 (AngIotensin II Receptor 2), a member of the G protein-coupled receptor (GPCR) family, specifically designed to bind angiotensin II (Ang II). Angiotensin II is a peptide hormone that plays a crucial role in the renin-angiotensin system (RAS). AT2R is primarily expressed in embryonic tissues and is associated with blood pressure regulation, nerve growth, pain control, and myocardial regeneration. Drugs targeting AT2R can improve cardiovascular function and alleviate neuropathic pain. In the nervous system, AT2R is related to pain mechanisms, primarily expressed in the dorsal root ganglia and trigeminal ganglion. Damaged nerves and pain neuromas exhibit higher AT2R expression compared to normal nerves. Animal and clinical trials have demonstrated that AT2R antagonists can be used to relieve pain.
[0003] Neuropathic pain is a chronic pain disorder caused by primary damage or dysfunction of the nervous system. Based on the location of the lesion, it can be divided into peripheral neuropathic pain and central neuropathic pain. Trauma, inflammation, infection, or compression can all cause neuropathic pain, such as diabetic neuropathy (DNP), postherpetic neuralgia (PHN), primary neuropathy, secondary neuropathy, peripheral neuropathy, and neuropathic diseases caused by mechanical or biochemical nerve damage. Currently, the main drugs used clinically to treat neuropathic pain include antiepileptic drugs, antidepressants, and narcotic analgesics, such as gabapentin, pregabalin, and tricyclic antidepressants. However, these drugs lack specificity, have very limited therapeutic effects, and have serious side effects, including cognitive changes, sedation, nausea, and tolerance and dependence, far from meeting clinical needs.
[0004] Chinese invention patent application No. 202411407185.8 describes compound I-5 (the compound shown in formula (I) of this application) having AT2R antagonistic activity:
[0005] Based on the good biological activity of this compound, it is necessary to develop suitable salt forms and solid forms to obtain improved drug-like properties or other characteristics. Summary of the Invention
[0006] The present invention aims to solve at least one of the technical problems existing in the prior art.
[0007] The inventors of this application have developed a drug with AT2R antagonistic activity: (S)-3-((4-(3-(difluoromethoxy)-5-isobutyl-2-(2H-tetrazol-5-yl)phenyl)-2-methylpiperazin-1-yl)methyl)pyridazine (the compound shown in formula (I)). To find a solid form with better druggability, the inventors conducted extensive experimental research to obtain the crystal form of the compound shown in formula (I), various salts, and their crystal forms. These crystal forms possess advantages such as high purity and good stability, and can serve as AT2R antagonists.
[0008] In a first aspect, the present invention provides a solid form of a compound as shown in formula (I).
[0009] I; Wherein, the solid form of the compound shown in formula (I) is amorphous, crystalline, salt and crystalline form of its salt.
[0010] In one embodiment, the amorphous form of the compound represented by formula (I) has an X-ray powder diffraction pattern that is essentially as follows: Figure 1 As shown.
[0011] In one embodiment, the crystal form of the compound represented by formula (I) is a first free state crystal form and a second free state crystal form.
[0012] In one embodiment, the first free state crystal form of the compound represented by formula (I) is free state crystal form A.
[0013] In one embodiment, the second free state crystal form of the compound represented by formula (I) is free state crystal form B.
[0014] In one embodiment, the crystal form of the compound represented by formula (I) is either free crystal form A or free crystal form B.
[0015] In one embodiment, the salt of the compound represented by formula (I) and the crystal form of the salt are salts formed by the compound with an acid or a base and the crystal form of the salt; the acid includes oxalic acid; the base includes at least one of sodium hydroxide and potassium hydroxide.
[0016] In one embodiment, the salt of the compound represented by formula (I) and the crystal form of the salt are the salt formed by the compound with an acid or a base and the crystal form of the salt; the acid is selected from oxalic acid; and the base is selected from sodium hydroxide or potassium hydroxide.
[0017] In one embodiment, the salt of the compound represented by formula (I) is an oxalate, sodium salt, or potassium salt.
[0018] In one embodiment, the crystal form of the compound salt represented by formula (I) is a first oxalate crystal form, a second oxalate crystal form, a sodium salt crystal form, or a potassium salt crystal form.
[0019] In one embodiment, the first oxalate crystal form of the compound represented by formula (I) is oxalate crystal form A.
[0020] In one embodiment, the second oxalate crystal form of the compound represented by formula (I) is oxalate crystal form B.
[0021] In one embodiment, the sodium salt crystal form of the compound represented by formula (I) is sodium salt crystal form A.
[0022] In one embodiment, the sodium salt crystal form of the compound represented by formula (I) is sodium salt crystal form B.
[0023] In one embodiment, the crystal form of the compound salt represented by formula (I) is oxalate crystal form A, oxalate crystal form B, sodium salt crystal form A, or potassium salt crystal form A.
[0024] This invention provides a first free crystal form of a compound as shown in formula (I).
[0025] I The X-ray powder diffraction pattern of the first free crystal form has diffraction peaks at the following 2θ angles: 5.7±0.2°, 14.1±0.2°, 16.6±0.2°, and 18.9±0.2°.
[0026] The “2θ or 2θ angle” mentioned in this disclosure refers to the diffraction angle, where θ is the Bragg angle, and the unit is ° or degree; the error range of 2θ for each characteristic peak is ±0.2 (including the case where the number with more than one decimal place is rounded to the nearest even number).
[0027] In one embodiment, the X-ray powder diffraction pattern of the first free-state crystal form also has diffraction peaks at one or more of the following 2θ angles: 9.9±0.2°, 10.3±0.2°, 11.2±0.2°, 12.4±0.2°, 20.5±0.2°, 21.5±0.2°, 22.0±0.2°, 22.8±0.2°, and 26.6±0.2°.
[0028] In one embodiment, the X-ray powder diffraction pattern of the first free-state crystal form has diffraction peaks at 5.7±0.2°, 10.3±0.2°, 11.2±0.2°, 14.1±0.2°, 16.6±0.2°, 18.9±0.2°, and 21.5±0.2°.
[0029] In one embodiment, the X-ray powder diffraction pattern of the first free-state crystal form has diffraction peaks at 5.7±0.2°, 9.9±0.2°, 10.3±0.2°, 11.2±0.2°, 12.4±0.2°, 14.1±0.2°, 16.6±0.2°, 18.9±0.2°, and 21.5±0.2°.
[0030] In one embodiment, the X-ray powder diffraction pattern of the first free-state crystal form has diffraction peaks at 5.7±0.2°, 9.9±0.2°, 10.3±0.2°, 11.2±0.2°, 12.4±0.2°, 14.1±0.2°, 16.6±0.2°, 18.9±0.2°, 20.5±0.2°, 21.5±0.2°, and 22.8±0.2°.
[0031] In one embodiment, the X-ray powder diffraction pattern of the first free-state crystal form has diffraction peaks at 5.7±0.2°, 9.9±0.2°, 10.3±0.2°, 11.2±0.2°, 12.4±0.2°, 14.1±0.2°, 16.6±0.2°, 18.9±0.2°, 20.5±0.2°, 21.5±0.2°, 22.0±0.2°, 22.8±0.2°, and 26.6±0.2°.
[0032] In one embodiment, the X-ray powder diffraction pattern of the first free-state crystal form, including the positions and relative intensities of the diffraction peaks, is essentially as shown in Table 7: Table 7 .
[0033] In one embodiment, the first free state crystal form is free state crystal form A, and the X-ray powder diffraction pattern of the free state crystal form A is essentially as follows: Figure 2 As shown.
[0034] In one embodiment, the first free state crystal form is free state crystal form A, and the differential scanning calorimetry analysis of the free state crystal form A shows an endothermic peak at 154.5±3 °C.
[0035] In one embodiment, the first free crystal form is free crystal form A, and the thermogravimetric analysis chart of free crystal form A shows a weight loss of 1.09±3% at 150℃±3℃.
[0036] In one embodiment, the first free state crystal form is free state crystal form A, and the differential scanning calorimetry analysis curve of the free state crystal form A is shown below. Figure 3 As shown.
[0037] In one embodiment, the first free state crystal form is free state crystal form A, and the thermogravimetric analysis diagram of free state crystal form A is shown below. Figure 3 As shown.
[0038] In one embodiment, the first free state crystal form is free state crystal form A, and the variable temperature X-ray powder diffraction pattern of the free state crystal form A is as follows: Figure 5 As shown.
[0039] This invention provides a free crystal form A of the compound shown in formula (I).
[0040] I The X-ray powder diffraction pattern of the free crystal form A has diffraction peaks at the following 2θ angles: 5.7±0.2°, 14.1±0.2°, 16.6±0.2°, and 18.9±0.2°.
[0041] The “2θ or 2θ angle” mentioned in this disclosure refers to the diffraction angle, where θ is the Bragg angle, and the unit is ° or degree; the error range of 2θ for each characteristic peak is ±0.2 (including the case where the number with more than one decimal place is rounded to the nearest even number).
[0042] In one embodiment, the X-ray powder diffraction pattern of the free crystal form A also has diffraction peaks at one or more of the following 2θ angles: 9.9±0.2°, 10.3±0.2°, 11.2±0.2°, 12.4±0.2°, 20.5±0.2°, 21.5±0.2°, 22.0±0.2°, 22.8±0.2°, and 26.6±0.2°.
[0043] In one embodiment, the X-ray powder diffraction pattern of the free crystal form A has diffraction peaks at 5.7±0.2°, 10.3±0.2°, 11.2±0.2°, 14.1±0.2°, 16.6±0.2°, 18.9±0.2°, and 21.5±0.2°.
[0044] In one embodiment, the X-ray powder diffraction pattern of the free crystal form A has diffraction peaks at 5.7±0.2°, 9.9±0.2°, 10.3±0.2°, 11.2±0.2°, 12.4±0.2°, 14.1±0.2°, 16.6±0.2°, 18.9±0.2°, and 21.5±0.2°.
[0045] In one embodiment, the X-ray powder diffraction pattern of the free crystal form A has diffraction peaks at 5.7±0.2°, 9.9±0.2°, 10.3±0.2°, 11.2±0.2°, 12.4±0.2°, 14.1±0.2°, 16.6±0.2°, 18.9±0.2°, 20.5±0.2°, 21.5±0.2°, and 22.8±0.2°.
[0046] In one embodiment, the X-ray powder diffraction pattern of the free crystal form A has diffraction peaks at 5.7±0.2°, 9.9±0.2°, 10.3±0.2°, 11.2±0.2°, 12.4±0.2°, 14.1±0.2°, 16.6±0.2°, 18.9±0.2°, 20.5±0.2°, 21.5±0.2°, 22.0±0.2°, 22.8±0.2°, and 26.6±0.2°.
[0047] In one embodiment, the X-ray powder diffraction pattern of the free crystal form A, including the positions and relative intensities of the diffraction peaks, is essentially as shown in Table 7: Table 7 .
[0048] In one embodiment, the X-ray powder diffraction pattern of the free crystal form A is essentially as follows: Figure 2 As shown.
[0049] In one embodiment, the differential scanning calorimetry (DSC) analysis of the free crystal form A shows an endothermic peak at 154.5 ± 3 °C.
[0050] In one embodiment, the free crystal form A shows a weight loss of 1.09±3% at 150℃±3℃ in its thermogravimetric analysis.
[0051] In one embodiment, the differential scanning calorimetry (DSC) analysis of the free crystal form A is shown in the figure below. Figure 3 As shown.
[0052] In one embodiment, the thermogravimetric analysis diagram of the free crystal form A is as follows: Figure 3 As shown.
[0053] In one embodiment, the variable-temperature X-ray powder diffraction pattern of the free-state crystal form A is as follows: Figure 5As shown.
[0054] The present invention also provides a second free crystal form of the compound shown in formula (I).
[0055] I The X-ray powder diffraction pattern of the second free-state crystal form has diffraction peaks at the following 2θ angles: 7.0±0.2°, 8.4±0.2°, 11.5±0.2°, and 14.5±0.2°.
[0056] In one embodiment, the X-ray powder diffraction pattern of the second free-state crystal form also has diffraction peaks at one or more of the following 2θ angles: 7.3±0.2°, 13.6±0.2°, 14.0±0.2°, 17.6±0.2°, 21.6±0.2°, and 21.9±0.2°.
[0057] In one embodiment, the X-ray powder diffraction pattern of the second free-state crystal form has diffraction peaks at 7.0±0.2°, 8.4±0.2°, 13.6±0.2°, 14.0±0.2°, and 14.5±0.2°.
[0058] In one embodiment, the X-ray powder diffraction pattern of the second free-state crystal form has diffraction peaks at 7.0±0.2°, 8.4±0.2°, 11.5±0.2°, 13.6±0.2°, 14.0±0.2°, 14.5±0.2°, and 17.6±0.2°.
[0059] In one embodiment, the X-ray powder diffraction pattern of the second free-state crystal form has diffraction peaks at 7.0±0.2°, 7.3±0.2°, 8.4±0.2°, 11.5±0.2°, 14.0±0.2°, 14.5±0.2°, and 17.6±0.2°.
[0060] In one embodiment, the X-ray powder diffraction pattern of the second free-state crystal form shows diffraction peaks at 7.0±0.2°, 7.3±0.2°, 8.4±0.2°, 11.5±0.2°, 13.6±0.2°, 14.0±0.2°, 14.5±0.2°, 17.6±0.2°, and 21.9±0.2°.
[0061] In one embodiment, the X-ray powder diffraction pattern of the second free-state crystal form shows diffraction peaks at 7.0±0.2°, 7.3±0.2°, 8.4±0.2°, 11.5±0.2°, 13.6±0.2°, 14.0±0.2°, 14.5±0.2°, 17.6±0.2°, 21.6±0.2°, and 21.9±0.2°.
[0062] In one embodiment, the X-ray powder diffraction pattern of the second free-state crystal form, including the positions and relative intensities of the diffraction peaks, is essentially as shown in Table 8: Table 8 .
[0063] In one embodiment, the second free state crystal form is free state crystal form B, and the X-ray powder diffraction patterns of the sample of free state crystal form B before and after drying are superimposed as follows. Figure 6 As shown.
[0064] In one embodiment, the second free state crystal form is free state crystal form B, and the differential scanning spectroscopy analysis of the free state crystal form B shows an endothermic peak at 53.4 ºC ± 3 ℃.
[0065] In one embodiment, the second free crystal form is free crystal form B, and the thermogravimetric analysis chart of free crystal form B shows a weight loss of 4.32±3% at 150℃±3℃.
[0066] In one embodiment, the second free state crystal form is free state crystal form B, and the differential scanning calorimetry analysis curve of the free state crystal form B is shown below. Figure 7 As shown.
[0067] In one embodiment, the second free state crystal form is free state crystal form B, and the thermogravimetric analysis diagram of the free state crystal form B is shown below. Figure 7 As shown.
[0068] In one embodiment, the second free state crystal form is free state crystal form B, and the X-ray powder diffraction patterns of the free state crystal form B before and after the heating experiment are as follows. Figure 9 As shown.
[0069] The present invention also provides a method for preparing the first free crystal form of the compound shown in formula (I), wherein the compound shown in formula (I) is dissolved in a solvent and stirred at room temperature to obtain the first free crystal form; the solvent is H2O, an organic solvent or a mixed solvent, preferably H2O, CHCl3, MIBK, MTBE, EtOAc, EtOH, MEK, IPAc, THF, Acetone, DCM, 1,4-Dioxane, MeOH, Anisole, 2-MeTHF or ACN; the mixed solvent is a mixed solvent of organic solvent and water, a mixed solvent of organic solvent and n-Heptane or a mixed solvent of organic solvent and IPE; the mixed solvent is preferably a mixed solvent of CHCl3 and n-Heptane, a mixed solvent of EtOH and n-Heptane, or a mixed solvent of EtOAc and n-Heptane.
[0070] The present invention also provides a method for preparing the first free crystal form of the compound shown in formula (I), wherein the compound shown in formula (I) is dissolved in a solvent and stirred at room temperature to obtain the first free crystal form; the solvent is an organic solvent or a mixed solvent, preferably CHCl3, MIBK, MTBE, EtOAc, EtOH, MEK, IPAc, THF, Acetone, DCM, 1,4-Dioxane, MeOH, Anisole, 2-MeTHF or ACN; the mixed solvent is a mixed solvent of organic solvent and water, a mixed solvent of organic solvent and n-Heptane, or a mixed solvent of organic solvent and IPE; the mixed solvent is preferably a mixed solvent of CHCl3 and n-Heptane, a mixed solvent of EtOH and n-Heptane, or a mixed solvent of EtOAc and n-Heptane.
[0071] In one embodiment, the method for preparing the first free crystal form involves adding the compound shown in formula (I) to a mixed solvent, stirring at room temperature, centrifuging to separate the solid, and drying under vacuum at room temperature or 50°C to obtain the first free crystal form.
[0072] In one embodiment, in the method for preparing the first free crystal form, the mixed solvent is a mixture of two solvents that have been thoroughly mixed before being added.
[0073] In one embodiment, in the method for preparing the first free crystal form, the mixed solvent is prepared by first adding one solvent and then adding another solvent.
[0074] In one embodiment, in the method for preparing the first free crystal form, the volume ratio of the mixed solvent is selected from (0.5-2):1.
[0075] In one embodiment, the preparation method of the first free crystal form involves a mixed solvent volume ratio of 1:1.
[0076] In one embodiment, in the method for preparing the first free crystal form, the mixed solvent is selected from CHCl3 / n-Heptane (1:1, V / V), EtOH / n-Heptane (0.5:1.5, V / V), and EtOAc / n-Heptane (1:1, V / V).
[0077] In one embodiment, the room temperature stirring time in the preparation method of the first free crystal form is selected from 0.5 days, 1 day, 2 days or 3 days.
[0078] The present invention also provides a method for preparing the first free state crystal form of the compound shown in formula (I), wherein the compound shown in formula (I) is dissolved in a solvent, a small amount of seed crystals are added to the system, and the mixture is stirred at room temperature to obtain the first free state crystal form; the solvent is H2O, an organic solvent or a mixed solvent, preferably H2O, CHCl3, MIBK, MTBE, EtOAc, EtOH, MEK, IPAc, THF, Acetone, DCM, 1,4-Dioxane, MeOH, Anisole, 2-MeTHF or ACN; the mixed solvent is a mixture of an organic solvent and water, a mixture of an organic solvent and n-Heptane or a mixture of an organic solvent and IPE; the mixed solvent is preferably a mixture of EtOH and n-Heptane.
[0079] The present invention also provides a method for preparing the first free state crystal form of the compound shown in formula (I), wherein the compound shown in formula (I) is dissolved in a solvent, a small amount of seed crystals are added to the system, and the mixture is stirred at room temperature to obtain the first free state crystal form; the solvent is an organic solvent or a mixed solvent, preferably CHCl3, MIBK, MTBE, EtOAc, EtOH, MEK, IPAc, THF, Acetone, DCM, 1,4-Dioxane, MeOH, Anisole, 2-MeTHF or ACN; the mixed solvent is a mixture of organic solvent and water, a mixture of organic solvent and n-Heptane, or a mixture of organic solvent and IPE; the mixed solvent is preferably a mixture of EtOH and n-Heptane.
[0080] In one embodiment, the method for preparing the first free crystal form involves dissolving the compound shown in formula (I) in EtOH, adding a small amount of seed crystals of the first free crystal form to the clear solution, slowly adding n-Heptane in batches, stirring at room temperature, centrifuging to separate the solid, and vacuum drying at room temperature to obtain the first free crystal form.
[0081] In one embodiment, in the method for preparing the first free crystal form, the volume ratio of EtOH to n-Heptane is selected from 1:(1-5).
[0082] In one embodiment, in the method for preparing the first free crystal form, the volume ratio of EtOH and n-Heptane is selected from 1:3.
[0083] The present invention also provides a method for preparing a second free crystal form of a compound as shown in formula (I), wherein the compound shown in formula (I) is dissolved in a solvent, and then an antisolvent is added and allowed to stand at room temperature to obtain the second free crystal form; the solvent is preferably 1,4-Dioxane or ACN; the antisolvent is preferably IPE, n-Pentane or H2O.
[0084] The present invention also provides an oxalate of the compound shown in formula (I).
[0085] In one embodiment, the oxalate of the compound shown in formula (I) is the first oxalate crystal form of the compound shown in formula (I).
[0086] In one embodiment, the X-ray powder diffraction pattern of the first oxalate crystal form has diffraction peaks at 6.8±0.2°, 8.9±0.2°, 19.3±0.2°, and 19.7±0.2°.
[0087] In one embodiment, the X-ray powder diffraction pattern of the first oxalate crystal form also has diffraction peaks at one or more of the following 2θ angles: 7.4±0.2°, 11.9±0.2°, 17.7±0.2°, 20.5±0.2°, 21.5±0.2°, and 24.0±0.2°.
[0088] In one embodiment, the X-ray powder diffraction pattern of the first oxalate crystal form has diffraction peaks at 6.8±0.2°, 7.4±0.2°, 8.9±0.2°, 19.3±0.2°, 19.7±0.2°, and 20.5±0.2°.
[0089] In one embodiment, the X-ray powder diffraction pattern of the first oxalate crystal form has diffraction peaks at 6.8±0.2°, 7.4±0.2°, 8.9±0.2°, 17.7±0.2°, 19.3±0.2°, 19.7±0.2°, 20.5±0.2°, and 24.0±0.2°.
[0090] In one embodiment, the X-ray powder diffraction pattern of the first oxalate crystal form has diffraction peaks at 6.8±0.2°, 7.4±0.2°, 8.9±0.2°, 11.9±0.2°, 17.7±0.2°, 19.3±0.2°, 19.7±0.2°, 20.5±0.2°, 21.5±0.2°, and 24.0±0.2°.
[0091] In one embodiment, the X-ray powder diffraction pattern of the first oxalate crystal form, including the positions and relative intensities of the diffraction peaks, is essentially as shown in Table 9: Table 9
[0092] In one embodiment, the first oxalate crystal form is oxalate crystal form A, and the X-ray powder diffraction pattern of oxalate crystal form A is as follows: Figure 11 As shown.
[0093] In one embodiment, the first oxalate crystal form is oxalate crystal form A, and the differential scanning spectroscopy analysis of oxalate crystal form A shows an endothermic peak at 88.6 ºC ± 3 ℃.
[0094] In one embodiment, the first oxalate crystal form is oxalate crystal form A, and the thermogravimetric analysis chart of oxalate crystal form A shows a weight loss of 5.47±3% at 100℃±3℃.
[0095] In one embodiment, the first oxalate crystal form is oxalate crystal form A, and the differential scanning calorimetry analysis curve of oxalate crystal form A is shown below. Figure 12 As shown.
[0096] In one embodiment, the first oxalate crystal form is oxalate crystal form A, and the thermogravimetric analysis diagram of oxalate crystal form A is shown below. Figure 12 As shown.
[0097] In one embodiment, the first oxalate crystal form comprises the compound shown in formula (I) and oxalic acid, wherein the molar ratio of the compound shown in formula (I) to oxalic acid is (0.5~2):(0.5~2).
[0098] In one embodiment, the first oxalate crystal form comprises the compound shown in formula (I) and oxalic acid, wherein the molar ratio of the compound shown in formula (I) to oxalic acid is (0.9~1.6):(0.9~1.6).
[0099] In one embodiment, the first oxalate crystal form comprises the compound shown in formula (I) and oxalic acid, wherein the molar ratio of the compound shown in formula (I) to oxalic acid is 1.4:1.
[0100] In one embodiment, the first oxalate crystal form comprises the compound shown in formula (I) and oxalic acid, wherein the molar ratio of the compound shown in formula (I) to oxalic acid is 1:1.4.
[0101] In one embodiment, the first oxalate crystal form comprises the compound shown in formula (I) and oxalic acid, wherein the molar ratio of the compound shown in formula (I) to oxalic acid is 1:1.5.
[0102] The present invention also provides a method for preparing the first oxalate crystal form of the compound shown in formula (I), wherein the compound shown in formula (I), oxalic acid, and solvent are mixed and pulped at room temperature to obtain the first oxalate crystal form; wherein the solvent is a polar solvent.
[0103] In one embodiment, in the method for preparing the first oxalate crystal form, the equivalent ratio of the compound shown in formula (I) to oxalic acid is (0.5-2):1.
[0104] In one embodiment, in the method for preparing the first oxalate crystal form, the equivalent ratio of the compound shown in formula (I) to oxalic acid is 1:1.
[0105] In one embodiment, in the method for preparing the first oxalate crystal form, the mass-to-volume ratio of the compound represented by formula (I) to the solvent is 10-50 mg / mL.
[0106] In one embodiment, in the method for preparing the first oxalate crystal form, the mass-to-volume ratio of the compound represented by formula (I) to the solvent is 40 mg / mL.
[0107] In one embodiment, the polar solvent in the method for preparing the first oxalate crystal form is selected from ACN.
[0108] In one embodiment, the preparation method of the first oxalate crystal form includes a room temperature pulping time of 1-5 days.
[0109] In one embodiment, the room temperature pulping time in the preparation method of the first oxalate crystal form is selected from 3 days.
[0110] In one embodiment, the oxalate of the compound shown in formula (I) is the second oxalate crystal form of the compound shown in formula (I).
[0111] In one embodiment, the X-ray powder diffraction pattern of the second oxalate crystal form has diffraction peaks at 8.5±0.2°, 10.6±0.2°, 14.3±0.2°, 18.2±0.2°, and 22.4±0.2°.
[0112] In one embodiment, the X-ray powder diffraction pattern of the second oxalate crystal form also has diffraction peaks at one or more of the following 2θ angles: 7.4±0.2°, 11.9±0.2°, 17.7±0.2°, 20.5±0.2°, 21.5±0.2°, and 24.0±0.2°.
[0113] In one embodiment, the X-ray powder diffraction pattern of the second oxalate crystal form has diffraction peaks at 6.8±0.2°, 7.4±0.2°, 8.9±0.2°, 19.3±0.2°, 19.7±0.2°, and 20.5±0.2°.
[0114] In one embodiment, the X-ray powder diffraction pattern of the second oxalate crystal form has diffraction peaks at 6.8±0.2°, 7.4±0.2°, 8.9±0.2°, 17.7±0.2°, 19.3±0.2°, 19.7±0.2°, 20.5±0.2°, and 24.0±0.2°.
[0115] In one embodiment, the X-ray powder diffraction pattern of the second oxalate crystal form has diffraction peaks at 6.8±0.2°, 7.4±0.2°, 8.9±0.2°, 11.9±0.2°, 17.7±0.2°, 19.3±0.2°, 19.7±0.2°, 20.5±0.2°, 21.5±0.2°, and 24.0±0.2°.
[0116] In one embodiment, the X-ray powder diffraction pattern of the second oxalate crystal form, including the positions and relative intensities of the diffraction peaks, is essentially as shown in Table 10: Table 10 .
[0117] In one embodiment, the second oxalate crystal form is oxalate crystal form B, and the X-ray powder diffraction pattern of oxalate crystal form B is shown below. Figure 14 As shown.
[0118] In one scheme, the second oxalate crystal form is oxalate crystal form B, and the differential scanning spectroscopy analysis of oxalate crystal form B shows an endothermic peak at 145.1 ºC ± 3 ℃.
[0119] In one embodiment, the second oxalate crystal form is oxalate crystal form B, and the thermogravimetric analysis chart of oxalate crystal form B shows a weight loss of 1.33±3% at 120℃±3℃.
[0120] In one embodiment, the second oxalate crystal form is oxalate crystal form B, and the differential scanning calorimetry analysis chromatogram of oxalate crystal form B is shown below. Figure 15 As shown.
[0121] In one embodiment, the second oxalate crystal form is oxalate crystal form B, and the thermogravimetric analysis diagram of oxalate crystal form B is shown below. Figure 15 As shown.
[0122] In one embodiment, the second oxalate crystal form comprises the compound shown in formula (I) and oxalic acid, wherein the molar ratio of the compound shown in formula (I) to oxalic acid is (0.5~2):(0.5~2).
[0123] In one embodiment, the second oxalate crystal form comprises the compound shown in formula (I) and oxalic acid, wherein the molar ratio of the compound shown in formula (I) to oxalic acid is (0.9~1.1):(0.9~1.1).
[0124] In one embodiment, the second oxalate crystal form comprises the compound shown in formula (I) and oxalic acid, wherein the molar ratio of the compound shown in formula (I) to oxalic acid is 1:0.9.
[0125] In one embodiment, the second oxalate crystal form comprises the compound shown in formula (I) and oxalic acid, wherein the molar ratio of the compound shown in formula (I) to oxalic acid is 0.9:1.
[0126] In one embodiment, the second oxalate crystal form comprises the compound shown in formula (I) and oxalic acid, wherein the molar ratio of the compound shown in formula (I) to oxalic acid is 1:1.
[0127] The present invention also provides a method for preparing a second oxalate crystal form of the compound shown in formula (I), wherein the compound shown in formula (I), oxalic acid, and solvent are mixed and pulped to obtain the second oxalate crystal form; wherein the solvent is a nonpolar solvent.
[0128] In one embodiment, in the method for preparing the second oxalate crystal form, the equivalent ratio of the compound shown in formula (I) to oxalic acid is (0.5-2):1.
[0129] In one embodiment, in the method for preparing the second oxalate crystal form, the equivalent ratio of the compound shown in formula (I) to oxalic acid is 1:1.
[0130] In one embodiment, in the method for preparing the second oxalate crystal form, the mass-to-volume ratio of the compound represented by formula (I) to the solvent is 10-50 mg / mL.
[0131] In one embodiment, in the method for preparing the second oxalate crystal form, the mass-to-volume ratio of the compound represented by formula (I) to the solvent is 40 mg / mL.
[0132] In one embodiment, the nonpolar solvent in the preparation method of the second oxalate crystal form is selected from EtOAc or MIBK.
[0133] In one embodiment, the pulping time in the preparation method of the second oxalate crystal form is selected from 1-5 days.
[0134] In one embodiment, the pulping time in the preparation method of the second oxalate crystal form is selected from 3 days.
[0135] The present invention also provides a sodium salt of the compound shown in formula (I).
[0136] In one embodiment, the sodium salt of the compound shown in formula (I) is the sodium salt crystal form of the compound shown in formula (I).
[0137] In one embodiment, the X-ray powder diffraction pattern of the sodium salt crystal form has diffraction peaks at 4.9±0.2°, 9.7±0.2°, 17.6±0.2°, 18.7±0.2°, and 19.6±0.2°.
[0138] In one embodiment, the X-ray powder diffraction pattern of the sodium salt crystal form also has diffraction peaks at one or more of the following 2θ angles: 12.4±0.2°, 13.6±0.2°, 15.0±0.2°, 16.7±0.2°, 16.9±0.2°, 24.1±0.2°, and 27.1±0.2°.
[0139] In one embodiment, the X-ray powder diffraction pattern of the sodium salt crystal form has diffraction peaks at 4.9±0.2°, 9.7±0.2°, 15.0±0.2°, 16.7±0.2°, 17.6±0.2°, 18.7±0.2°, and 19.6±0.2°.
[0140] In one embodiment, the X-ray powder diffraction pattern of the sodium salt crystal form exhibits diffraction peaks at 4.9±0.2°, 9.7±0.2°, 13.6±0.2°, 15.0±0.2°, 16.7±0.2°, 17.6±0.2°, 18.7±0.2°, 19.6±0.2°, and 24.1±0.2°.
[0141] In one embodiment, the X-ray powder diffraction pattern of the sodium salt crystal form exhibits diffraction peaks at 4.9±0.2°, 9.7±0.2°, 12.4±0.2°, 13.6±0.2°, 15.0±0.2°, 16.7±0.2°, 16.9±0.2°, 17.6±0.2°, 18.7±0.2°, 19.6±0.2°, 24.1±0.2°, and 27.1±0.2°.
[0142] In one embodiment, the X-ray powder diffraction pattern of the sodium salt crystal form contains diffraction peak positions and relative intensities, which are essentially as shown in Table 11: Table 11 .
[0143] In one embodiment, the sodium salt crystal form is sodium salt crystal form A, and the X-ray powder diffraction pattern of sodium salt crystal form A is as follows: Figure 17 As shown.
[0144] In one embodiment, the sodium salt crystal form is sodium salt crystal form A, and the differential scanning spectroscopy analysis of sodium salt crystal form A shows two endothermic peaks at 43.6±3 ℃ and 87.9 ºC±3 ℃.
[0145] In one embodiment, the sodium salt crystal form is sodium salt crystal form A, and the differential scanning spectroscopy analysis of sodium salt crystal form A shows an endothermic peak at 43.6±3 °C.
[0146] In one embodiment, the sodium salt crystal form is sodium salt crystal form A, and the differential scanning spectroscopy analysis of sodium salt crystal form A shows an endothermic peak at 87.9 ºC ± 3 ℃.
[0147] In one embodiment, the sodium salt crystal form is sodium salt crystal form A, and the thermogravimetric analysis chart of sodium salt crystal form A shows a weight loss of 9.04±3% at 100℃±3℃.
[0148] In one embodiment, the sodium salt crystal form is sodium salt crystal form A, and the differential scanning calorimetry analysis chromatogram of sodium salt crystal form A is shown below. Figure 18 As shown.
[0149] In one embodiment, the sodium salt crystal form is sodium salt crystal form A, and the thermogravimetric analysis (TGA) curve of sodium salt crystal form A is shown below. Figure 18 As shown.
[0150] In one embodiment, the sodium salt crystal form A comprises the compound shown in formula (I) and sodium ions, wherein the molar ratio of the compound shown in formula (I) to the sodium ions is (0.5~2.5):(0.5~2.5).
[0151] In one embodiment, the sodium salt crystal form A comprises the compound shown in formula (I) and sodium ions, wherein the molar ratio of the compound shown in formula (I) to the sodium ions is (0.9~2.5):(0.9~2.5).
[0152] In one embodiment, the sodium salt crystal form A comprises the compound shown in formula (I) and sodium ions, wherein the molar ratio of the compound shown in formula (I) to sodium ions is 1:2.2.
[0153] In one embodiment, the sodium salt crystal form A comprises the compound shown in formula (I) and sodium ions, wherein the molar ratio of the compound shown in formula (I) to the sodium ions is 1:2.
[0154] The present invention also provides a method for preparing the sodium salt crystal form of the compound shown in formula (I), wherein the compound shown in formula (I), sodium hydroxide, and solvent are mixed and slurryed at room temperature to obtain the sodium salt crystal form; wherein the solvent is a nonpolar solvent.
[0155] In one embodiment, the sodium salt crystal form is prepared by mixing the compound shown in formula (I), 1 equivalent of NaOH and MIBK, slurrying at room temperature for 1-3 days, centrifuging to separate the solid and vacuum drying at 50°C to obtain the sodium salt crystal form.
[0156] In one embodiment, the pulping time in the method for preparing the sodium salt crystal form is 2 days.
[0157] The present invention also provides a potassium salt of the compound shown in formula (I).
[0158] In one embodiment, the potassium salt of the compound shown in formula (I) is the potassium salt crystal form of the compound shown in formula (I).
[0159] In one embodiment, the X-ray powder diffraction pattern of the potassium salt crystal form has diffraction peaks at 5.1±0.2°, 10.1±0.2°, 17.3±0.2°, 17.6±0.2°, and 22.2±0.2°.
[0160] In one embodiment, the X-ray powder diffraction pattern of the potassium salt crystal form also exhibits diffraction peaks at one or more of the following 2θ angles: 11.5±0.2°, 12.0±0.2°, 12.2±0.2°, 12.7±0.2°, 13.8±0.2°, 15.2±0.2°, 16.7±0.2°, 19.2±0.2°, 20.5±0.2°, 21.7±0.2°, 23.1±0.2°, 23.8±0.2°, 25.5±0.2°, and 28.7±0.2°.
[0161] In one embodiment, the X-ray powder diffraction pattern of the potassium salt crystal form has diffraction peaks at 5.1±0.2°, 10.1±0.2°, 12.7±0.2°, 17.3±0.2°, 17.6±0.2°, 19.2±0.2°, 21.7±0.2°, 22.2±0.2°, and 28.7±0.2°.
[0162] In one embodiment, the X-ray powder diffraction pattern of the potassium salt crystal form exhibits diffraction peaks at 5.1±0.2°, 10.1±0.2°, 12.0±0.2°, 12.7±0.2°, 13.8±0.2°, 17.3±0.2°, 17.6±0.2°, 19.2±0.2°, 21.7±0.2°, 22.2±0.2°, 23.8±0.2°, and 28.7±0.2°.
[0163] In one embodiment, the X-ray powder diffraction pattern of the potassium salt crystal form exhibits diffraction peaks at 5.1±0.2°, 10.1±0.2°, 11.5±0.2°, 12.0±0.2°, 12.7±0.2°, 13.8±0.2°, 15.2±0.2°, 17.3±0.2°, 17.6±0.2°, 19.2±0.2°, 21.7±0.2°, 22.2±0.2°, 23.1±0.2°, 23.8±0.2°, 25.5±0.2°, and 28.7±0.2°.
[0164] In one embodiment, the X-ray powder diffraction pattern of the potassium salt crystal form exhibits diffraction peaks at 5.1±0.2°, 10.1±0.2°, 11.5±0.2°, 12.0±0.2°, 12.2±0.2°, 12.7±0.2°, 13.8±0.2°, 15.2±0.2°, 16.7±0.2°, 17.3±0.2°, 17.6±0.2°, 19.2±0.2°, 20.5±0.2°, 21.7±0.2°, 22.2±0.2°, 23.1±0.2°, 23.8±0.2°, 25.5±0.2°, and 28.7±0.2°.
[0165] In one embodiment, the X-ray powder diffraction pattern of the potassium salt crystal form contains diffraction peak positions and relative intensities, which are basically as shown in Table 12: Table 12 .
[0166] In one embodiment, the potassium salt crystal form is potassium salt crystal form A, and the X-ray powder diffraction pattern of potassium salt crystal form A is as follows: Figure 20 As shown.
[0167] In one embodiment, the potassium salt crystal form is potassium salt crystal form A, and the differential scanning spectroscopy analysis of potassium salt crystal form A shows two endothermic peaks at 80.3±3 ℃ and 144.9 ºC±3 ℃.
[0168] In one embodiment, the potassium salt crystal form is potassium salt crystal form A, and the differential scanning spectroscopy analysis of potassium salt crystal form A shows an endothermic peak at 80.3±3 °C.
[0169] In one embodiment, the potassium salt crystal form is potassium salt crystal form A, and the differential scanning spectroscopy analysis of potassium salt crystal form A shows an endothermic peak at 144.9 ºC ± 3 ℃.
[0170] In one embodiment, the potassium salt crystal form is potassium salt crystal form A, and the thermogravimetric analysis chart of potassium salt crystal form A shows a weight loss of 7.41±3% at 100℃±3℃.
[0171] In one embodiment, the potassium salt crystal form is potassium salt crystal form A, and the differential scanning calorimetry analysis chromatogram of potassium salt crystal form A is shown below. Figure 21 As shown.
[0172] In one embodiment, the potassium salt crystal form is potassium salt crystal form A, and the thermogravimetric analysis diagram of potassium salt crystal form A is shown below. Figure 21 As shown.
[0173] In one embodiment, the potassium salt crystal form includes the compound shown in formula (I) and potassium ions, wherein the molar ratio of the compound shown in formula (I) to potassium ions is (0.5~2):(0.5~2).
[0174] In one embodiment, the potassium salt crystal form comprises the compound shown in formula (I) and potassium ions, wherein the molar ratio of the compound shown in formula (I) to potassium ions is (0.9~1.1):(0.9~1.1).
[0175] In one embodiment, the potassium salt crystal form comprises the compound shown in formula (I) and potassium ions, wherein the molar ratio of the compound shown in formula (I) to potassium ions is 1:1.
[0176] The present invention also provides a method for preparing the potassium salt crystal form of the compound shown in formula (I), wherein the compound shown in formula (I), potassium hydroxide, and solvent are mixed and slurryed at room temperature to obtain the potassium salt crystal form; wherein the solvent is a nonpolar solvent.
[0177] In one scheme, the method for preparing the potassium salt crystal form involves mixing the compound shown in formula (I), 1 equivalent of KOH and MIBK, slurrying at room temperature for 1-3 days, centrifuging to separate the solid, and vacuum drying at 50°C to obtain the potassium salt crystal form.
[0178] In one embodiment, the pulping time in the method for preparing the potassium salt crystal form is 2 days.
[0179] According to embodiments of the present invention, those skilled in the art will understand that when the compound of formula (I) forms a salt with a base, the molar ratio of the compound of formula (I) to the base can be 5:1 to 1:5, for example 3:1, 2:1, 1:1, 1:1.5, 1:2, 1:2.5, or 1:3. The base is an inorganic base as described above.
[0180] According to embodiments of the present invention, those skilled in the art will understand that when the compound of formula (I) forms a salt with an acid, the molar ratio of the compound of formula (I) to the acid can be 5:1 to 1:5, for example 3:1, 2:1, 1:1, 1:1.5, 1:2, 1:2.5, or 1:3. The acid is one of the aforementioned organic acids.
[0181] The present invention also provides a pharmaceutical composition comprising any crystal form of a compound of formula (I), a salt thereof, or a combination thereof. In some embodiments, the pharmaceutical composition further comprises a pharmaceutically acceptable carrier, excipient, diluent, adjuvant, or a combination thereof.
[0182] In some embodiments, the salt in the pharmaceutical composition of the present invention may be any crystal form of the salt, specifically any crystal form of the salt or any combination thereof.
[0183] In some embodiments, the pharmaceutical composition of the present invention comprises any salt of the compound represented by formula (I), or a crystal form of any salt of the present invention, or any crystal form of the salt and any combination thereof.
[0184] This invention provides the use of the crystal form of the compound represented by formula (I), the crystal form of its salts, or combinations thereof, or the use of the pharmaceutical composition in the preparation of a medicament, the use including: Prevention and / or treatment of AT2R-mediated diseases; And / or, to prevent and / or treat diseases for which a reduction in Ang II action is desired or required; And / or, to prepare a drug, pharmaceutical composition or formulation as an AT2R antagonist.
[0185] Crystal forms of the compounds represented by formula (I), crystal forms of their salts or combinations thereof, or pharmaceutical compositions thereof are provided that are intended for use in the treatment of neuropathies or neuropathic pain.
[0186] This invention provides the use of the crystal form of the compound represented by formula (I), its salt, crystal form of its salt, or combinations thereof, or the pharmaceutical composition thereof in the preparation of a medicament for treating and / or preventing AT2R-mediated diseases. The salt of the compound represented by formula (I) is any one or more of the crystal forms, salts, or crystal forms of their salts described above.
[0187] The present invention provides a method for treating and / or preventing AT2R-mediated diseases, comprising administering a therapeutically effective dose of the salt or pharmaceutical composition of the present invention to a human or animal.
[0188] In some embodiments, the AT2R-mediated disease described in this invention is neuropathy or neuropathic pain.
[0189] In some embodiments, the disease is postherpetic neuralgia or diabetic peripheral neuropathy.
[0190] Definitions and general terms Unless otherwise stated, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. All patents and publications related to this invention are incorporated herein by reference in their entirety. Although any methods and substances similar to or identical to those described herein may be used in the practice or testing of this invention, preferred methods, apparatus, and substances are described herein.
[0191] In this article, the ordinal numbers such as "first," "second," and "third" used before crystal forms are only used to distinguish different crystal forms and do not have any substantial meaning of sequence or order. For example, "first sodium salt crystal form" and "second sodium salt crystal form" indicate two different sodium salt crystal forms.
[0192] "Solid form" refers to a state of matter with a fixed volume and shape, a hard texture, and tightly bonded atoms. This includes crystalline forms, amorphous forms, salts, and crystalline forms of salts.
[0193] "Crystal form" or "crystalline form" refers to a solid with a highly regular chemical structure, including, but not limited to, single-component or multi-component crystals, and / or polymorphs of compounds, solvates, hydrates, inclusion compounds, eutectics, solvates of salts, and hydrates of salts.
[0194] "Amorphous" or "amorphous" refers to matter formed when the particles (molecules, atoms, ions) of a substance are arranged in a non-periodic manner in three-dimensional space.
[0195] "Salts of the compounds shown in formula (I)" refers to salts formed by the reaction of the compounds shown in (I) (in free state) with various suitable acids or bases, including oxalates, sodium salts, potassium salts, etc., as described in this invention.
[0196] "Crystal form of salt" refers to the different crystalline forms that salts of the same compound (such as the hydrochloride or sulfate of a drug) form in the solid state through different molecular arrangements, conformations, or combinations with different solvent / water molecules. This includes, but is not limited to, amorphous forms, solvates, and eutectic forms.
[0197] X-ray powder diffraction (XRPD) can detect changes in crystal form, crystallinity, and crystal structure, and is a commonly used method for identifying crystal forms. The peak positions in XRPD spectra depend primarily on the crystal structure and are relatively insensitive to experimental details, while their relative peak heights depend on many factors related to sample preparation and instrument geometry. Therefore, in some embodiments, the crystal form of the present invention is characterized by an XRPD spectrum with certain peak positions, which is essentially as shown in the XRPD spectrum provided in the accompanying drawings. Furthermore, the measurement of 2θ in XRPD spectra can be subject to experimental error; the measurement of 2θ in XRPD spectra may vary slightly between different instruments and different samples, therefore the value of 2θ should not be considered absolute. In the context of this invention, 2θ values in X-ray powder diffraction patterns are expressed in degrees (°). In some embodiments, diffraction peaks have a range of ±0.2°. o Error tolerance.
[0198] Differential scanning calorimetry (DSC) is a technique that measures the energy difference between a sample and an inert reference (commonly α-Al₂O₃) as a function of temperature by continuously heating or cooling under programmed control. Therefore, in some embodiments, the crystal form described in this invention is substantially as shown in the DSC diagram provided in the accompanying drawings. However, DSC spectra may be subject to experimental error; the peak positions and peak values may vary slightly between different instruments and different samples. Therefore, the peak positions or peak values of the DSC endothermic peaks should not be considered absolute.
[0199] Thermogravimetric analysis (TGA) is a technique used under programmed control to determine the change in mass of a substance with temperature. It is suitable for examining the loss of solvent in crystals or the sublimation and decomposition of samples, and can infer the presence of water of crystallization or crystallization solvent in the crystal. The mass change shown by the TGA curve depends on many factors, such as sample preparation and instrumentation; the mass change detected by TGA varies slightly between different instruments and different samples.
[0200] The term "basically as shown" means that at least 50%, or at least 60%, or at least 70%, or at least 80%, or at least 90%, or at least 95%, or at least 99% of the peaks in an X-ray powder diffraction pattern, DSC pattern, Raman spectrum, or infrared spectrum are shown in the pattern.
[0201] In this application, RH refers to relative humidity. It is defined as the ratio of the actual water vapor content (absolute humidity) in the air at a specific temperature to the saturated water vapor content at the same temperature, usually expressed as a percentage (%).
[0202] In the context of this invention, when using, or regardless of whether, terms such as “about” or “approximately” are used (e.g., temperature or temperature range), it means within 10% of a given value or range, appropriately within 5%, and particularly within 1%. Alternatively, for those skilled in the art, the term “about” or “approximately” means within an acceptable standard error range of the average value. Whenever a number with a value of N is disclosed, any number having a value within N+ / –1%, N+ / –2%, N+ / –3%, N+ / –5%, N+ / –7%, N+ / –8%, or N+ / –10% is within an acceptable range, where “+ / –” means addition or subtraction.
[0203] Unless otherwise indicated, the structural formulas described in this invention include all isomers (e.g., enantiomers, diastereomers, and geometric isomers (or conformational isomers)): for example, R and S configurations containing an asymmetric center, (Z) and (E) isomers of double bonds, and (Z) and (E) conformational isomers. Therefore, any single stereochemical isomer of the compounds of this invention, or its enantiomers, diastereomers, or mixtures of geometric isomers (or conformational isomers), is within the scope of this invention.
[0204] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Attached Figure Description
[0205] The above and / or additional aspects and advantages of the present invention will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which: Figure 1 This is the XRPD spectrum of an amorphous sample of compound I obtained according to Example 1 of the present invention.
[0206] Figure 2 This is the XRPD spectrum of the free crystal form A of compound I obtained according to Example 2 of the present invention.
[0207] Figure 3 This is the TGA / DSC spectrum of the free crystal form A of compound I obtained according to Example 2 of the present invention.
[0208] Figure 4 It is the free crystal form A of compound I obtained according to Example 2 of the present invention. 1 H NMR spectrum.
[0209] Figure 5 This is a VT-XRPD overlay of the free crystal form A of compound I obtained according to Example 2 of the present invention.
[0210] Figure 6 This is an XRPD overlay image of the free crystal form B of compound I obtained according to Example 3 of the present invention before and after drying.
[0211] Figure 7 This is the TGA / DSC spectrum of the free crystal form B of compound I obtained according to Example 3 of the present invention.
[0212] Figure 8 It is the free crystal form B of compound I obtained according to Example 3 of the present invention. 1 H NMR spectrum.
[0213] Figure 9This is an XRPD overlay image of the free crystal form B of compound I obtained according to Example 3 of the present invention before and after the heating experiment.
[0214] Figure 10 The free crystal form B of compound I obtained according to Example 3 of the present invention was subjected to a heating experiment. 1 H NMR spectrum.
[0215] Figure 11 This is the XRPD spectrum of oxalate crystal form A obtained according to Example 4 of the present invention.
[0216] Figure 12 The image shows the TGA / DSC spectrum of oxalate crystal form A obtained according to Example 4 of the present invention.
[0217] Figure 13 It is the oxalate crystal form A obtained according to Example 4 of the present invention. 1 H NMR spectrum.
[0218] Figure 14 This is the XRPD spectrum of oxalate crystal form B obtained according to Example 4 of the present invention.
[0219] Figure 15 This is the TGA / DSC spectrum of oxalate crystal form B obtained according to Example 4 of the present invention.
[0220] Figure 16 It is the oxalate crystal form B obtained according to Example 4 of the present invention. 1 H NMR spectrum.
[0221] Figure 17 This is the XRPD spectrum of sodium salt crystal form A obtained according to Example 5 of the present invention.
[0222] Figure 18 This is the TGA / DSC spectrum of sodium salt crystal form A obtained according to Example 5 of the present invention.
[0223] Figure 19 It is the sodium salt crystal form A obtained according to Example 5 of the present invention. 1 H NMR spectrum.
[0224] Figure 20 This is the XRPD spectrum of potassium salt crystal form A obtained according to Example 6 of the present invention.
[0225] Figure 21 The image shows the TGA / DSC spectrum of potassium salt crystal form A obtained according to Example 6 of the present invention.
[0226] Figure 22 It is the potassium salt crystal form A obtained according to Example 6 of the present invention. 1 H NMR spectrum.
[0227] Figure 23 The graph shows the dynamic solubility curves of free crystal form A obtained according to Example 7 of the present invention in H2O, SGF, FaSSIF and FeSSIF at 37°C.
[0228] Figure 24 This is an XRPD overlay image of the solubility sample of free crystal form A of compound I in H2O according to Example 7 of the present invention.
[0229] Figure 25 This is an XRPD overlay image of the solubility sample of free crystal form A of compound I in SGF according to Example 7 of the present invention.
[0230] Figure 26 This is an XRPD overlay of the solubility sample of free crystal form A of compound I according to Example 7 of the present invention in FaSSIF.
[0231] Figure 27 This is an XRPD overlay image of the solubility sample of free crystal form A of compound I in FeSSIF according to Example 7 of the present invention.
[0232] Figure 28 This is a DVS diagram of the free crystal form A according to Example 8 of the present invention.
[0233] Figure 29 This is an XRPD overlay image of free crystal form A before and after testing according to Example 8 of the present invention.
[0234] Figure 30 This is an XRPD overlay image of the sample obtained from the solid stability evaluation of the free crystal form A of compound I according to Example 9 of the present invention under different influencing factors. Detailed Implementation
[0235] The embodiments of the present invention are described in detail below. These embodiments are exemplary and are only used to explain the present invention, and should not be construed as limiting the invention. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in the art or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all commercially available conventional products.
[0236] Symbols or units: IC 50 The half-maximum inhibitory concentration (MCC) is the concentration at which half of the maximum inhibitory effect is achieved. M: mol / L, for example, n-butyllithium (14.56 mL, 29.1 mmol, 2.5 M n-hexane solution) means a n-butyllithium n-hexane solution with a molar concentration of 2.5 mol / L; N: Equivalent concentration, for example, 2N hydrochloric acid means a 2 mol / L hydrochloric acid solution.
[0237] General Experiment 1. Instrument Information and Methods X-ray powder diffraction (XRPD) XRPD images were acquired using a PANalytacal Empyrean X-ray powder diffractometer and a Bruker D8 ADVANCE. The scanning parameters are shown in Table 13.
[0238] Table 13: XRPD Test Parameters
[0239] Thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) The TGA and DSC plots were acquired on a TA TGA5500 thermogravimetric analyzer and a TA TGA250 / 2500 differential scanning calorimeter, respectively. The test parameters are listed in Table 14.
[0240] Table 14: TGA and DSC Test Parameters
[0241] Liquid NMR ( 1 H NMR) Liquid NMR spectra were acquired on a Bruker 400M NMR spectrometer using deuterated dimethyl sulfoxide (DMSO-d6) as the solvent.
[0242] Ultra-high performance liquid chromatography and ion chromatography (UPLC / IC) The purity, dynamic solubility, and stability results in the experiment were obtained using a Waters H-Class ultra-high performance liquid chromatograph, and the ion salt molar ratio was determined by ion chromatography. The analytical conditions are shown in Tables 15 and 16.
[0243] Table 15: Liquid Chromatography Test Conditions
[0244] Table 16: Ion Chromatography Test Conditions
[0245] Ultra-high performance liquid chromatography-mass spectrometry (UPLC-MS) The LC-MS data in the experiment were obtained by an Agilent 1290 ultra-high performance liquid chromatograph equipped with a single quadrupole mass spectrometer detector, and the analytical conditions are shown in Figure 17.
[0246] Table 17: UPLC-MS Test Conditions
[0247] Dynamic moisture adsorption (DVS) Dynamic moisture adsorption (DVS) curves were acquired using the DVSIntrInsic on an SMS (Surface Measurement Systems) device. Relative humidity at 25 ºC was corrected for the deliquescence points of LiCl, Mg(NO3)2, and KCl. DVS test parameters are shown in Table 18.
[0248] Table 18: Dynamic Moisture Adsorption Test Conditions
[0249] Solvent English-Chinese Glossary Table 19 shows the abbreviations of solvents and their corresponding Chinese names.
[0250] Table 19: Chinese-English Glossary
[0251] Example 1: Preparation method of compound I In this embodiment of the invention, the preparation method of (S)-3-((4-(3-(difluoromethoxy)-5-isobutyl-2-(2H-tetrazol-5-yl)phenyl)-2-methylpiperazin-1-yl)methyl)pyridazine (compound I) is described in reference to patent CN202411407185.8, and its structure is shown below.
[0252] I The synthesis route is shown below:
[0253]
[0254] Step 1: Synthesis of tert-butyl (S)-3-methyl-4-(pyridazine-3-ylmethyl)piperazine-1-carboxylate
[0255] Triethylamine (2.4 g, 23.4 mmol) and (S)-3-methylpiperazine-1-carboxylic acid tert-butyl ester (1.56 g, 7.8 mmol) were added to a solution of N,N-dimethylformamide (10 mL) containing 3-(chloromethyl)pyridazine (1 g, 7.8 mmol), and the mixture was stirred at 50 °C for 18 h. The reaction mixture was poured into water (100 mL) and extracted three times with ethyl acetate (50 mL). The organic phase was dried over anhydrous sodium sulfate, filtered, and concentrated to obtain the crude product. The crude product was purified by column chromatography (petroleum ether / ethyl acetate (V / V) = 1 / 0-1 / 1) to give the product (S)-3-methyl-4-(pyridazine-3-ylmethyl)piperazine-1-carboxylic acid tert-butyl ester (1.8 g, 79% yield).
[0256] LC-MS, M / Z (ESI): 293.4 [M+H] + Step 2: Synthesis of (S)-3-((2-methylpiperazin-1-yl)methyl)pyridazine
[0257] Hydrochloric acid / 1,4-dioxane (9 mL, 4 M) was added to a solution of dioxane (1.8 g, 6.2 mmol) containing (S)-3-methyl-4-(pyridazin-3-ylmethyl)piperazine-1-carboxylate tert-butyl ester (9 mL), and the reaction was carried out at room temperature for 2 h. The reaction solution was concentrated to give the product (S)-3-((2-methylpiperazin-1-yl)methyl)pyridazine (1.5 g, hydrochloride).
[0258] LC-MS, M / Z (ESI): 193.3 [M+H] + Step 3: Synthesis of 1-(4-bromophenylmethyl)-2-(trifluoromethyl)-1H-imidazolium
[0259] To a solution of dioxane (50 mL) containing 4-bromo-2-fluoro-6-hydroxybenzonitrile (5 g, 23.1 mmol) and isobutylboronic acid (5.88 g, 57.7 mmol), [1,1'-bis(diphenylphosphine)ferrocene]palladium dichloride (1.68 g, 2.3 mmol) and potassium carbonate (9.6 g, 69.3 mmol) were added, purging with argon three times. The reaction mixture was then reacted at argon atmosphere and 110 °C for 18 h. The reaction solution was poured into water (200 mL) and extracted three times with ethyl acetate (100 mL). The organic phase was washed twice with saturated brine (100 mL), dried over anhydrous sodium sulfate, filtered, and concentrated to obtain the crude product. The crude product was purified by column chromatography (petroleum ether / ethyl acetate (V / V) = 1 / 0-0 / 1) to give the product 2-fluoro-6-hydroxy-4-isobutylbenzonitrile (3.2 g, yield 71.5%).
[0260] LC-MS, M / Z (ESI): 194.3 [M+H] + Step 4: Synthesis of 2-(difluoromethoxy)-6-fluoro-4-isobutylbenzonitrile
[0261] At -78°C, potassium hydroxide (9.3 g, 166 mmol, dissolved in 32 mL of water) was added to an acetonitrile (32 mL) solution containing 2-fluoro-6-hydroxy-4-isobutylbenzonitrile (3.2 g, 16.6 mmol), followed by the slow addition of diethyl bromodifluoromethylphosphonate (8.9 g, 33.2 mmol). The mixture was slowly brought to room temperature and stirred at room temperature for 18 h. The reaction mixture was poured into water (100 mL) and extracted three times with ethyl acetate (50 mL). The organic phase was washed twice with saturated brine (20 mL), dried over anhydrous sodium sulfate, filtered, and concentrated to obtain the crude product. The crude product was purified by column chromatography (petroleum ether / ethyl acetate (V / V) = 1 / 00 / 1) to give the product 2-(difluoromethoxy)-6-fluoro-4-isobutylbenzonitrile (1.6 g, 40% yield).
[0262] Step 5: Synthesis of (S)-2-(difluoromethoxy)-4-isobutyl-6-(3-methyl-4-(pyridazin-3-methyl)piperazin-1-yl)benzonitrile
[0263] To a solution of N,N-dimethylformamide (16 mL) containing 2-(difluoromethoxy)-6-fluoro-4-isobutylbenzonitrile (1.6 g, 6.6 mmol), (S)-3-((2-methylpiperazin-1-yl)methyl)pyridazine (1.9 g, 9.9 mmol) and N,N-diisopropylethylamine (2.6 g, 19.8 mmol) were added, and the mixture was stirred at 80 °C for 18 h. The reaction solution was poured into water (100 mL) and then extracted three times with ethyl acetate (50 mL). The organic phase was washed twice with saturated brine (50 mL), dried over anhydrous sodium sulfate, filtered, and concentrated to obtain the crude product. The crude product was purified by column chromatography (petroleum ether / ethyl acetate (V / V) = 1 / 0-0 / 1) to give the product (S)-2-(difluoromethoxy)-4-isobutyl-6-(3-methyl-4-(pyridazine-3-methyl)piperazine-1-yl)benzonitrile (900 mg, yield 33%).
[0264] LC-MS, M / Z (ESI): 416.3 [M+H] + Step 6: Synthesis of (S)-3-((4-(3-(difluoromethoxy)-5-isobutyl-2-(2H-tetrazol-5-yl)phenyl)-2-methylpiperazin-1-yl)methyl)pyridazine
[0265] (S)-2-(difluoromethoxy)-4-isobutyl-6-(3-methyl-4-(pyridazin-3-methyl)piperazin-1-yl)benzonitrile (300 mg, 0.7 mmol), sodium azide (364 mg, 5.6 mmol), and tributyltin chloride (1.8 g, 5.6 mmol) were dissolved in toluene (3 mL). The solution was poured into the inner liner of a stainless steel sealed container and reacted at 140 °C for 6 h. The reaction solution was slowly poured into water (50 mL) and extracted three times with ethyl acetate (20 mL). The organic phase was washed twice with saturated brine (10 mL), dried over anhydrous sodium sulfate, filtered, and concentrated to obtain the crude product. The crude product was prepared by reverse phase chromatography (column: Phenomenex Synergi C18 100*25mm* 4um; solvent: A = water + 0.1 vol% formic acid (99%), B = acetonitrile; gradient: 5%-95%, 7 min) to obtain product (S)-3-((4-(3-(difluoromethoxy)-5-isobutyl-2-(2H-tetrazol-5-yl)phenyl)-2-methylpiperazin-1-yl)methyl)pyridazine (42 mg, purity 96.86%, yield 12.7%).
[0266] XRPD, such as Figure 1As shown, the obtained compound sample of formula I is basically in an amorphous state.
[0267] LC-MS, M / Z (ESI): 459.3 [M+H] + 1 H NMR (400 MHz, DMSO-d6) δ 9.10 (dd, 1H), 7.68 – 7.60 (m, 2H), 7.11(t, 1H), 6.90 (s, 1H), 6.85 (s, 1H), 4.04 (d, 1H), 3.61 (d, 1H), 2.81 – 2.65(m, 3H), 2.55 – 2.50 (m, 2H), 2.47 (s, 2H), 2.38 – 2.30 (m, 1H), 2.13 – 2.05(m, 1H), 1.93 – 1.83 (m, 1H), 0.87 (dd, 9H). Example 2: Preparation of free crystal form A of compound I Method 1: Weigh 20 mg of compound I obtained in Example 1 and add it to a 5 mL sample vial. Add 0.1-0.2 mL of CHCl3 and stir at room temperature until the sample dissolves. Add 0.1-0.2 mL of n-Heptane to form an oil. Stir the oil sample at room temperature overnight to precipitate a solid. Centrifuge to separate the solid and air dry at room temperature. Perform X-ray powder diffraction (XRPD), thermogravimetric analysis (TGA), and differential scanning calorimetry (DSC) to determine the solid. Name it free crystal form A. The X-ray powder diffraction results are as follows: Figure 2 As shown in Table 7, the XRPD diffraction peak data of the free crystal form A are presented. The DSC results show that the sample has one endothermic peak at 154.5 ºC (peak temperature). 1 ¹H NMR results showed no solvent residue in the sample. The free crystalline form A exhibited a 1.09% weight loss at 150 °C using TGA. Crystallography of the free crystalline form A was performed using VT-XRPD, and the results showed no change in crystal form after purging the sample under N₂ for 20 min, heating it to 120 °C under N₂ protection, and cooling it to room temperature. Thermogravimetric analysis is as follows: Figure 3 As shown, the results of differential scanning calorimetry Figure 3 As shown, 1 The H NMR results are as follows Figure 4 As shown, the results of VT-XRPD are as follows: Figure 5 As shown.
[0268] Table 7: XRPD diffraction peak data of free crystal form A
[0269] Method 2: Weigh out about 300 mg of compound I prepared in Example 1 and add it to a 12 mL sample bottle. Add 4 mL of ethyl acetate / n-heptane (1:1, V / V), stir at room temperature for 1 day, centrifuge to separate the solid and vacuum dry at 50 °C to obtain the solid. Perform XPRD test to show that it is free crystal form A.
[0270] Method 3: Weigh out about 1 g of compound I prepared in Example 1 and add it to a 50 mL sample bottle. Add 4 mL of ethyl acetate / n-heptane (1:1, V / V), stir at room temperature for 3 days, centrifuge to separate the solid and vacuum dry at room temperature to obtain the solid. Perform XPRD test to show that it is free crystal form A.
[0271] Method 4: Weigh approximately 100 mg of compound I prepared in Example 1 into a 10 mL sample vial, add 0.5 mL of ethanol, and sonicate at room temperature until the sample dissolves. Add a small amount of free crystal form A seed to the clear solution. Then add 0.125 mL of n-heptane and stir at room temperature for 10 minutes. Slowly add 1.375 mL of n-heptane to the above sample vial, continue stirring at room temperature for 12 hours, centrifuge to separate the solid, and vacuum dry at room temperature to obtain the solid. XPRD testing shows that it is free crystal form A.
[0272] Example 3: Screening of polymorphs of compound I in its free state (1) Room temperature suspension stirring Approximately 20 mg of compound I (free crystalline form A prepared in Example 2) was weighed into each 2 mL transparent sample vial. 0.3–0.5 mL of solvent was added to each vial. The resulting suspension was magnetically stirred at room temperature for 3 days, and then the solid was separated by centrifugation. The solid obtained in the sample vial was vacuum dried at room temperature and then subjected to XRPD testing. The results are shown in Table 20.
[0273] Table 20: Room Temperature Suspension Stirring
[0274] 1: The sample was stirred at room temperature until it became clear, then stirred at 5 ºC.
[0275] 2: The samples were clarified after stirring at room temperature / 5 ºC / -20 ºC, and then evaporated.
[0276] (2) Gas-liquid diffusion method Approximately 20 mg of compound I (the amorphous form prepared in Example 1) was weighed into each 3 mL transparent sample vial. 0.2–0.4 mL of solvent was added to each vial to obtain a clear solution. The solution was filtered through a 0.45 μm PTFE filter, and the filtrate was transferred to a 3 mL vial. Approximately 3 mL of antisolvent was added to a 20 mL vial. The 3 mL vial containing the filtrate was placed open over the 20 mL vial, and the 20 mL vial was sealed and allowed to stand at room temperature to precipitate a solid. The solid obtained in the sample vial was vacuum dried at room temperature and then subjected to XRPD testing. The results are shown in Table 21.
[0277] Table 21: Gas-Liquid Diffusion Method
[0278] The XRPD overlay images of the free crystal form B sample before and after drying when the solvent is 1,4-Dioxane and the antisolvent is H2O are shown below. Figure 6 As shown in Table 8, the XRPD diffraction peak data of the free crystal form B are shown. The TGA results show that the sample loses 4.32% of its weight when heated to 150 °C, and the DSC results show that the sample has an endothermic peak at 53.4 °C (peak temperature). 1 ¹H NMR results showed that the molar ratio of 1,4-Dioxane to free form in the sample was 0.04 (~0.8 wt%). Crystal form B of the free state was identified by heating experiments. The results showed that after heating the free state crystal form B to 100 ºC and exposing it to air, a shift in diffraction peaks was observed. The sample after heating... 1 ¹H NMR results showed that the molar ratio of 1,4-Dioxane to free 1,4-dioxane in the sample was 0.01 (~0.2 wt%). Thermogravimetric analysis was performed as follows. Figure 7 As shown, the results of differential scanning calorimetry Figure 7 As shown, 1 The H NMR results are as follows Figure 8 As shown, the XRPD results of free crystal form B before and after the heating experiment are as follows: Figure 9 As shown, the free-state crystal form B after heating experiment 1 The H NMR results are as follows Figure 10 As shown.
[0279] Table 8: XRPD diffraction peak data of free crystal form B
[0280] (3) Slow cooling method Approximately 20 mg of compound I (the amorphous form prepared in Example 1) was weighed into 3 mL transparent sample vials, and 0.9–1.0 mL of solvent was added. After stirring at 50 °C for approximately 2 hours, the mixture was filtered (using a PTFE filter with a pore size of 0.45 μm). The filtrate was then placed in a biochemical incubator and cooled from 50 °C to 5 °C at a rate of 0.05 °C / min. The solid was then separated by centrifugation and XRPD analysis was performed. The results are shown in Table 26.
[0281] Table 26: Slow Cooling Method
[0282] Note: 1: The sample turned into a white powder when stirred at 50 ºC, and then was stirred directly at room temperature.
[0283] 2: The sample becomes clear after slow cooling, and then evaporates.
[0284] (4) Antisolvent method Approximately 20 mg of compound I (the amorphous form prepared in Example 1) was weighed into 5 mL transparent sample vials. After dissolving in 0.1–0.2 mL of solvent, a poor solvent was added dropwise to the clear solution while stirring until solid precipitated. The process was stopped if no solid precipitated after adding a total of 5 mL of both solvents. The precipitated solid was separated by centrifugation and XRPD analysis was performed. The results are shown in Table 27.
[0285] Table 27: Antisolvent Method
[0286] Free crystalline form A can be obtained by room temperature pulping, slow cooling, and antisolvent method. XRPD shows that free crystalline form A has high crystallinity. DSC results indicate that it has an endothermic peak at 154.5 ºC (peak temperature). TGA results show that the sample loses approximately 1.09% weight when heated to 150 ºC, and there is no significant weight loss before sample decomposition. The XRPD diagram of free crystalline form A is shown below. Figure 11 As shown. The TGA / DSC plot of free crystal form A is shown below. Figure 12 As shown. Free-state crystalline form A exhibits favorable physicochemical properties, including high crystallinity, suitable endothermic peak temperature, and good pharmaceutical safety.
[0287] Starting with an amorphous form, free crystalline form B was obtained via gas-liquid diffusion in 1,4-Dioxane as the solvent and H₂O as the antisolvent. XRPD results showed that the crystallinity of the free crystalline form B decreased after drying. A shift in diffraction peaks was observed after heating the free crystalline form B to 100 °C and exposing it to air.
[0288] Example 4: Preparation of oxalate of compound I Approximately 20 mg of compound I (amorphous and free crystal form A) and 1 equivalent of oxalic acid were weighed into 2 mL transparent sample vials, respectively. The mixture was slurried in the solvent at room temperature for 3 days. The solids were separated by centrifugation and dried under vacuum at 50 °C. The results were then subjected to XRPD testing, and the results are shown in Table 28.
[0289] Table 28: Oxalate Screening Test
[0290] Note: *: The free crystal form A is used as the starting material, and the other systems are started from amorphous samples.
[0291] 1: After stirring the sample at room temperature until it forms a gel or oil, then stir at 50~5ºC.
[0292] Through screening of oxalates, two oxalate crystal forms were obtained, namely oxalate crystal form A and oxalate crystal form B.
[0293] The XRPD pattern of oxalate crystal form A sample is shown below. Figure 11 As shown in Table 9, the XRPD data is presented below. The TGA / DSC results are as follows: Figure 12 As shown, 1 The H NMR results are as follows Figure 13 As shown in the figure. TGA results show that the sample lost 5.47% of its weight when heated to 100 ºC; DSC results show that the sample had an endothermic peak at 88.6ºC (peak temperature). 1 ¹H NMR results showed no residual ACN solvent in the sample. HPLC / IC results showed that the molar ratio of oxalic acid to free oxalic acid in the sample was 1.4.
[0294] Table 9: XRPD diffraction peak data of oxalate crystal form A
[0295] The XRPD pattern of oxalate crystal form B sample is shown below. Figure 14 As shown in Table 10, the XRPD data is presented below. The TGA / DSC results are as follows: Figure 15 As shown, 1 The H NMR results are as follows Figure 16 As shown. TGA results show that the sample lost 1.33% of its weight when heated to 120ºC; DSC results show that the sample had an endothermic peak at 145.1ºC (peak temperature). 1 ¹H NMR results showed that the molar ratio of MIBK to free MIBK in the sample was 0.04 (~0.7 wt%). HPLC / IC results showed that the molar ratio of oxalic acid to free oxalic acid in the sample was 0.9.
[0296] Table 10: XRPD diffraction peak data of oxalate crystal form B
[0297] Example 5: Preparation of the sodium salt of compound I A certain amount of compound I in its free crystalline form A and 1 equivalent of NaOH were weighed into a transparent sample vial, and MIBK was added at room temperature. After slurrying at room temperature for about 2 days, the solid was separated by centrifugation and dried under vacuum at 50°C, followed by XRPD testing to obtain sodium salt crystalline form A.
[0298] The XRPD pattern of sodium salt crystal form A sample is shown below. Figure 17 As shown in Table 11, the XRPD data is presented below. The TGA / DSC results are as follows: Figure 18 As shown, 1 The H NMR results are as follows Figure 19 As shown in the figure. TGA results show that the sample lost 9.04% of its weight when heated to 100ºC; DSC results show that the sample had two endothermic peaks at 43.6 ºC and 87.9 ºC (peak temperature). 1 ¹H NMR results showed no solvent residue in the sample, and HPLC / IC results showed that the molar ratio of sodium ions to free sodium ions in the sample was 2.2.
[0299] Table 11: XRPD diffraction peak data of sodium salt crystal form A
[0300] Example 6: Preparation of the potassium salt of compound I A certain amount of compound I in its free crystalline form A and 1 equivalent of KOH were weighed into a transparent sample vial, and MIBK was added at room temperature. After slurrying at room temperature for about 2 days, the solid was separated by centrifugation and dried under vacuum at 50°C, followed by XRPD testing to obtain sodium salt crystalline form A.
[0301] The XRPD pattern of potassium salt crystal form A sample is shown below. Figure 20 As shown in Table 12, the XRPD data is presented below. The TGA / DSC results are as follows: Figure 21 As shown, 1 The H NMR results are as follows Figure 22 As shown in the figure. TGA results show that the sample lost 7.41% of its weight when heated to 100 ºC; DSC results show that the sample had two endothermic peaks at 80.3 ºC and 144.9 ºC (peak temperature). 1 ¹H NMR results showed no solvent residue in the sample. HPLC / IC results showed that the molar ratio of potassium ions to free potassium ions in the sample was 1.0.
[0302] Table 12: XRPD diffraction peak data of potassium salt crystal form A
[0303] Example 7: Dynamic Solubility The solid feed concentration was 10 mg / mL, and the mixture was rotary-mixed at 37 ºC. The solubility of free crystalline form A in H2O, SGF, FaSSIF, and FeSSIF was determined at different time points (1, 2, 4, and 24 hours). Samples were taken at each time point, centrifuged, and filtered. The HPLC concentration and pH of the filtrate were determined, and the XRPD of the centrifuged solid samples was tested. The results of the dynamic solubility test are summarized in Table 29.
[0304] Preparation of biological solvents Preparation of simulated gastric juice (SGF) Weigh 100 mg NaCl and 50 mg Trinaton X-100 into a 50 mL volumetric flask and dissolve in purified water. Add 816 μL of 1M hydrochloric acid and adjust the pH to 1.8 with 1M hydrochloric acid or 1M NaOH solution. Add purified water to bring the volume to a final volume.
[0305] Preparation of intestinal fluid simulating a fasting state (FaSSIF) Weigh 340 mg of anhydrous NaH₂PO₄ and 620 mg of NaCl into a 100 mL volumetric flask. Dissolve in purified water, then add 55.44 μL of 50% NaOH solution. Adjust the pH to 6.5 with 1M hydrochloric acid or 1M NaOH solution. Add purified water to bring the volume to a final volume. Then weigh 110 mg of SIF powder into a 50 mL volumetric flask, dissolve in the above solution, and bring the volume to a final volume.
[0306] Preparation of intestinal fluid simulating feeding conditions (FeSSIF) Take 0.82 mL of glacial acetic acid and 1.18 g of NaCl into a 100 mL volumetric flask, dissolve in purified water, then add 528 μL of 50% NaOH solution. Adjust the pH to 5.0 with 1M hydrochloric acid or 1M NaOH solution, add purified water, and bring to volume. Then weigh 560 mg of SIF powder into a 50 mL volumetric flask, dissolve in the above solution, and bring to volume.
[0307] Table 29: Summary of Dynamic Solubility Test Results at 37ºC
[0308] The dynamic solubility curve of free crystal form A at 37℃ is shown in the figure below. Figure 23 As shown.
[0309] XRPD overlay of the sample showing the solubility of free crystal form A in H2O is shown below. Figure 24 As shown.
[0310] XRPD overlay of the solubility of free crystal form A in SGF sample as shown in Figure 1. Figure 25 As shown.
[0311] The XRPD overlay of the sample's solubility in FaSSIF for free crystal form A is shown below. Figure 26 As shown.
[0312] XRPD overlay of the solubility of free crystal form A in FeSSIF sample as shown in the figure. Figure 27 As shown.
[0313] Dynamic solubility results showed that, compared to H2O, free crystalline form A exhibited varying degrees of increased solubility in SGF, FaSSIF, and FeSSIF, with higher solubility in SGF compared to the other solvents. XRPD results showed that no crystalline form change occurred in any sample after solubility testing.
[0314] Example 8: Hygroscopicity The hygroscopicity of free crystalline form A was assessed using a dynamic moisture adsorption (DVS) analyzer. The percentage change in sample mass was collected under constant temperature (25°C) as humidity varied (0%RH–95%RH). The DVS plot of free crystalline form A is shown below. Figure 28 As shown. The XRPD overlay images of free crystal form A before and after DVS testing are shown below. Figure 29 As shown in the figure. The results indicate that the water adsorption of free crystalline form A at 25 ºC / 80%RH is 0.2022%, indicating that the sample is slightly hygroscopic. XRPD results show that the crystal form of free crystalline form A remains unchanged after DVS testing, indicating high stability in high humidity environments.
[0315] Example 9: Solid stability The physical and chemical stability of the free crystalline form A was determined by XRPD and HPLC after being placed in a closed container at 80 °C for one day and in an open container at 25 °C / 60%RH and 40 °C / 75%RH for one week, respectively. The results of the solid stability tests are summarized in Table 30.
[0316] Table 30: Summary of Solid Stability Assessment
[0317] The XRPD overlay images of the sample obtained from the solid stability assessment of free crystal form A under different influencing factors are shown below. Figure 30 As shown.
[0318] Stability results showed that the crystal form and crystallinity of free crystal form A did not change significantly under different conditions.
[0319] In the test examples of this invention, the preparation method of the control compound is based on patent WO2023006893A1, and its structure is shown below.
[0320] Control compound.
[0321] Test Example 1: Compound Binding Test with AT2R The experimental procedure was performed according to the instructions of the Angiotensin AT2 Receptor Ligand Binding Assay kit (#C1TT1AT2, Cisbio). First, the 10 mM stock solution was serially diluted 5× (totaling 10 concentrations, with two replicates for each concentration), and 160 nL of each concentration was added to a 384-well plate. 40 μL of 1×TLB was added to each well, and the plate was vortexed at room temperature for 15 minutes. A 15 mL centrifuge tube containing 5 mL of 1×TLB was prepared beforehand. The frozen labeled cells were thawed in a 37°C water bath (1-2 minutes), and the thawed cells were quickly transferred to the aforementioned 15 mL centrifuge tube. After mixing, the cells were centrifuged at 1000g for 5 minutes at room temperature. The supernatant was discarded, and the cells were resuspended in 2.7 mL of 1×TLB. A new 384-well plate was prepared, and 10 μL of the mixed cells were added to the corresponding wells according to the experimental design. Add 5 μL of 4× compound solution and 5 μL of 4× Tag-lite red fluorescently labeled ligand to each well. After incubation at room temperature for 1 hour, data were read using EnVision's HTRF mode. The excitation light intensities at 665 nM and 615 nM were read in each well, and the ratio (Ratio = A665 nM / B615 nM) was calculated. The IC50 was calculated using GraphPad Prism8 software. 50 Numerical values, X: logarithmic value of compound concentration; Y: ratio of A665nM / B615nM.
[0322] Table 31: Binding activity of compounds with AT2R
[0323] Experimental results show that compound I of the present invention has a stronger binding ability to AT2R than the control compound.
[0324] Test Example 2: Rat Pharmacokinetic Test Pharmacokinetic studies were conducted on rats using three male SD rats (180-240g), which were fasted overnight and administered 10mg / kg orally via gavage. Blood samples were collected before administration and at 15, 30 minutes, 1, 2, 4, 6, 8, and 24 hours after administration. Blood samples were centrifuged at 8000 rpm for 6 minutes at 4°C, and plasma was collected and stored at -20°C. Plasma samples at each time point were mixed with 3-5 times the volume of acetonitrile solution containing an internal standard, vortexed for 1 minute, centrifuged at 13000 rpm for 10 minutes at 4°C, and the supernatant was mixed with 3 times the volume of water. An appropriate amount of the mixture was analyzed by LC-MS / MS. Key pharmacokinetic parameters were analyzed using a non-compartmental model with WinNonlin 7.0 software.
[0325] Experimental results show that the compound of the present invention has good pharmacokinetic properties in rats, which are superior to those of the control compound.
[0326] Test Example 3: Mouse Pharmacokinetic Study Pharmacokinetic studies were conducted in mice using three male ICR mice (20-30g each), which were fasted overnight and administered 10mg / kg orally via gavage. Blood samples were collected before administration and at 5, 15, and 30 minutes, and at 1, 2, 4, 6, 8, and 24 hours after administration. Blood samples were centrifuged at 6000g / min at 2-8℃ for 3 minutes, and plasma was collected and stored at -20℃. Plasma samples at each time point were mixed with 10 times the volume of 50% methanol-acetonitrile solution containing internal standard, vortexed for 5 minutes, centrifuged at 4000 rpm at 4℃ for 10 minutes, and the supernatant was mixed with 1 times the volume of water. An appropriate amount of the mixture was analyzed by LC-MS / MS. Key pharmacokinetic parameters were analyzed using a non-compartmental model with WinNonlin 7.0 software.
[0327] Experimental results show that the compounds of this invention have good pharmacokinetic properties in mice.
[0328] Test Example 4: Canine Pharmacokinetic Study Canine pharmacokinetic studies were conducted using three male Beagle dogs, weighing 10-12 kg, which were fasted overnight and administered 5 mg / kg orally via gavage. Blood samples were collected before administration and at 5, 15, and 30 minutes, and at 1, 2, 4, 6, 8, and 24 hours after administration. Blood samples were centrifuged at 6000 g / min at 2-8°C for 3 minutes, and plasma was collected and stored at -20°C. Plasma samples at each time point were mixed with 10 times the volume of 50% methanol-acetonitrile solution containing internal standard, vortexed for 5 minutes, centrifuged at 4000 rpm at 4°C for 5 minutes, and the supernatant was mixed with 1 times the volume of water. An appropriate amount of the mixture was analyzed by LC-MS / MS. Key pharmacokinetic parameters were analyzed using a non-compartmental model with WinNonlin 7.0 software.
[0329] Table 32: Results of canine pharmacokinetic studies
[0330] Experimental results show that the compound of the present invention has good pharmacokinetic characteristics in dogs, which are superior to those of the control compound.
[0331] Test Example 5: Manual Patch Clamp Technique for Detecting the Effect of Compounds on hERG Channel Current Manual patch-clamp assays were performed using the HEK-293 cell line, which stably expresses hERG potassium channels. hERG potassium channel cells were purchased from Creacell (catalog number: A-0320). The final concentrations of all test compounds were prepared on the same day and then dissolved in extracellular fluid. The extracellular fluid (mM) consisted of: 40 mM NaCl, 3.5 mM KCl, 1 mM MgCl₂•6H₂O, 2 mM CaCl₂•2H₂O, 10 mM D-Glucose, 10 mM HEPES, and 1.25 mM NaH₂PO₄•2H₂O; pH 7.4 (NaOH titration). The intracellular fluid (mM) consisted of: 20 mM KCl, 115 mM K-Aspartic, 1 mM MgCl₂·6H₂O, 5 mM EGTA, 10 mM HEPES, and 2 mM Na₂-ATP; pH 7.4 (KOH titration).
[0332] Electrophysiological experiments: After whole-cell sealing, the cell membrane voltage was clamped at -80 mV. The clamping voltage was depolarized from -80 mV to -50 mV and maintained for 0.5 s (as a leakage current detection), then stepped to 30 mV and maintained for 2.5 s, and then rapidly restored to -50 mV and maintained for 4 s to excite the peak tail current of the hERG channel. Data were collected every 10 s to observe the effect of the drug on the peak tail current of hERG. compound The effect of the drug was assessed. A 0.5 s -50 mV stimulus was used as the leakage current detection method. Drug administration began after the hERG current recorded in whole cells stabilized. Each drug concentration was administered for 5 minutes (or until the current stabilized) before proceeding to the next concentration. One or more concentrations were measured for each test compound. The peak tail current detected in each cell in a compound-free external solution was recorded. Control ( ) served as its own control group. Each concentration was tested independently in duplicate using at least two cells. All electrophysiological experiments were performed at room temperature. Experimental data were acquired using an IPA amplifier (Sutter Instrument) and stored in Sutter Patch software.
[0333] Data analysis: Calculate the inhibition rate (1-(Peak tail current)) corresponding to each drug concentration. compound / Peaktail current Control In GraphPad Prism software, a nonlinear fit was performed on the concentration-effect curves. The following equation was used to calculate the IC50 for each compound. 50 Value: Y = 1 / (1 + 10^((LogIC50 - X) * HillSlope)).
[0334] Table 33: Results of the inhibitory effect of compounds on hERG
[0335] Experimental results show that the compounds of this invention have a lower risk of inhibiting hERG in vitro and a weaker cardiac safety risk than the control compounds.
[0336] Test Example 6: Rat Model of Chronic Constrictive Sciatic Nerve Injury (CCI) Male SD rats weighing 200-250g were anesthetized and fixed in a prone position. The fur on the lateral thigh to the femur area was shaved and disinfected. A 1.5 cm incision was made in the thigh skin. The fascia was dissected, and the biceps femoris muscle was bluntly dissected to expose the sciatic nerve. The nerve was freed approximately 7 mm from the main trunk anterior to the trigeminal branch and gently dissected. The sciatic nerve was ligated four times with 5-0 sutures, spaced 1 mm apart, 2 mm anterior to the trigeminal branch, resulting in a ligated nerve length of approximately 4-5 mm. The ligation tightness was determined by the slight twitching of the calf muscles or toes when tying the knots. The muscles, subcutaneous tissue, and skin were sutured sequentially. The wound was cleaned and disinfected with iodine. The skin was sutured and disinfected. On the second day after modeling, the animals were randomly divided into groups of eight. Each group was orally administered either a solvent or a corresponding compound solution. The mechanical pain threshold of each animal was measured using Von-Frey fibers before and after administration.
[0337] Mechanical pain threshold detection method: The test animal's hind limb sole was continuously stimulated with Von-Frey fibers, causing the fibers to bend, and the animal's withdrawal response was observed. The test animal was stimulated sequentially according to the fiber weight, from smallest to largest, with each fiber weight being stimulated five times consecutively. If fewer than three positive responses occurred, the above procedure was repeated using a larger fiber weight. When three or more positive responses occurred on the first test, that fiber was considered the animal's pain threshold (three tests were conducted per animal, and the average value was taken). Fiber weights: 0.6, 1.0, 1.4, 2.0, 4.0, 6.0, 8.0, 10.0, 15.0; cut value: 15.0g. Data from each group were statistically analyzed using GraphPad Prism 8.0. One-way ANOVA was used to compare whether there were statistically significant differences between groups; P < 0.05 was considered statistically significant.
[0338] Experimental results show that, in a rat model of chronic sciatic nerve constriction injury, the compound of the present invention can significantly improve the decrease in mechanical pain threshold caused by sciatic nerve modeling in rats, and has excellent analgesic efficacy.
[0339] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0340] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.
Claims
1. A solid form of a compound of formula (I), I; in, The solid form of the compound represented by formula (I) is amorphous, crystalline, salt, and crystalline form of its salts.
2. The solid form of the compound of formula (I) according to claim 1, wherein the salt of the compound of formula (I) and the crystal form of the salt are salts formed by the compound with an acid or a base and the crystal form of the salt; wherein the acid includes oxalic acid; and wherein the base includes at least one of sodium hydroxide and potassium hydroxide.
3. The solid form of the compound of formula (I) according to claim 1, wherein the salt of the compound of formula (I) is an oxalate, a sodium salt or a potassium salt; and the crystal form of the salt of the compound of formula (I) is a first oxalate crystal form, a second oxalate crystal form, a sodium salt crystal form or a potassium salt crystal form; In the first oxalate crystal form, its X-ray powder diffraction pattern shows diffraction peaks at 6.8±0.2°, 8.9±0.2°, 19.3±0.2°, and 19.7±0.2°. In the second oxalate crystal form, its X-ray powder diffraction pattern shows diffraction peaks at 8.5±0.2°, 10.6±0.2°, 14.3±0.2°, 18.2±0.2°, and 22.4±0.2°. The sodium salt crystal form has X-ray powder diffraction patterns with diffraction peaks at 4.9±0.2°, 9.7±0.2°, 17.6±0.2°, 18.7±0.2°, and 19.6±0.2°. The potassium salt crystal form has X-ray powder diffraction patterns with diffraction peaks at 5.1±0.2°, 10.1±0.2°, 17.3±0.2°, 17.6±0.2°, and 22.2±0.2°.
4. The solid form of the compound of formula (I) according to claim 3, characterized in that, The first oxalate crystal form comprises the compound shown in formula (I) and oxalic acid, wherein the molar ratio of the compound shown in formula (I) to oxalic acid is (0.5~2):(0.5~2); preferably, the molar ratio of the compound shown in formula (I) to oxalic acid is (0.9~1.6):(0.9~1.6); preferably, the molar ratio of the compound shown in formula (I) to oxalic acid is 1:1.4; or The second oxalate crystal form comprises the compound shown in formula (I) and oxalic acid, wherein the molar ratio of the compound shown in formula (I) to oxalic acid is (0.5~2):(0.5~2); preferably, the molar ratio of the compound shown in formula (I) to oxalic acid is (0.9~1.1):(0.9~1.1); preferably, the molar ratio of the compound shown in formula (I) to oxalic acid is 1:1 or 1:0.9; or The sodium salt crystal form comprises the compound shown in formula (I) and sodium ions, wherein the molar ratio of the compound shown in formula (I) to sodium ions is (0.5~2.5):(0.5~2.5); preferably, the molar ratio of the compound shown in formula (I) to sodium ions is (0.9~2.5):(0.9~2.5); preferably, the molar ratio of the compound shown in formula (I) to sodium ions is 1:2.2; or The potassium salt crystal form includes the compound shown in formula (I) and potassium ions, wherein the molar ratio of the compound shown in formula (I) to potassium ions is (0.5~2):(0.5~2); preferably, the molar ratio of the compound shown in formula (I) to potassium ions is (0.9~1.1):(0.9~1.1); preferably, the molar ratio of the compound shown in formula (I) to potassium ions is 1:
1.
5. The solid form of the compound of formula (I) according to claim 1, characterized in that, The compound shown in formula (I) has either a first free state or a second free state crystal form. The X-ray powder diffraction pattern of the first free crystal form has diffraction peaks at the following 2θ angles: 5.7±0.2°, 14.1±0.2°, 16.6±0.2°, 18.9±0.2°; The X-ray powder diffraction pattern of the second free crystal form has diffraction peaks at the following 2θ angles: 7.0±0.2°, 8.4±0.2°, 11.5±0.2°, and 14.5±0.2°.
6. The solid form of the compound of formula (I) according to claim 3 or 5, characterized in that, The X-ray powder diffraction pattern of the first free-state crystal form satisfies one or more of the following conditions: (1a) It has diffraction peaks at one or more of the following 2θ angles: 9.9±0.2°, 10.3±0.2°, 11.2±0.2°, 12.4±0.2°, 20.5±0.2°, 21.5±0.2°, 22.0±0.2°, 22.8±0.2°, 26.6±0.2°; (1b) It has diffraction peaks at 5.7±0.2°, 10.3±0.2°, 11.2±0.2°, 14.1±0.2°, 16.6±0.2°, 18.9±0.2°, and 21.5±0.2°; (1c) It has diffraction peaks at 5.7±0.2°, 9.9±0.2°, 10.3±0.2°, 11.2±0.2°, 12.4±0.2°, 14.1±0.2°, 16.6±0.2°, 18.9±0.2°, and 21.5±0.2°; (1d) It has diffraction peaks at 5.7±0.2°, 9.9±0.2°, 10.3±0.2°, 11.2±0.2°, 12.4±0.2°, 14.1±0.2°, 16.6±0.2°, 18.9±0.2°, 20.5±0.2°, 21.5±0.2°, and 22.8±0.2°; (1e) It has diffraction peaks at 5.7±0.2°, 9.9±0.2°, 10.3±0.2°, 11.2±0.2°, 12.4±0.2°, 14.1±0.2°, 16.6±0.2°, 18.9±0.2°, 20.5±0.2°, 21.5±0.2°, 22.0±0.2°, 22.8±0.2°, and 26.6±0.2°; (1f) The positions of its diffraction peaks are shown in Table 1: Table 1 ; Alternatively, the X-ray powder diffraction pattern of the second free-state crystal form satisfies one or more of the following conditions: (2a) It has diffraction peaks at one or more of the following 2θ angles: 7.3±0.2°, 13.6±0.2°, 14.0±0.2°, 17.6±0.2°, 21.6±0.2°, 21.9±0.2°; (2b) It has diffraction peaks at 7.0±0.2°, 8.4±0.2°, 13.6±0.2°, 14.0±0.2°, and 14.5±0.2°; (2c) It has diffraction peaks at 7.0±0.2°, 8.4±0.2°, 11.5±0.2°, 13.6±0.2°, 14.0±0.2°, 14.5±0.2°, and 17.6±0.2°; (2d) It has diffraction peaks at 7.0±0.2°, 7.3±0.2°, 8.4±0.2°, 11.5±0.2°, 14.0±0.2°, 14.5±0.2°, and 17.6±0.2°; (2e) It has diffraction peaks at 7.0±0.2°, 7.3±0.2°, 8.4±0.2°, 11.5±0.2°, 13.6±0.2°, 14.0±0.2°, 14.5±0.2°, 17.6±0.2°, and 21.9±0.2°; (2f) It has diffraction peaks at 7.0±0.2°, 7.3±0.2°, 8.4±0.2°, 11.5±0.2°, 13.6±0.2°, 14.0±0.2°, 14.5±0.2°, 17.6±0.2°, 21.6±0.2°, and 21.9±0.2°; (2g) The positions of its diffraction peaks are shown in Table 1: Table 2 ; Alternatively, the X-ray powder diffraction pattern of the first oxalate crystal form satisfies one or more of the following conditions: (3a) It has diffraction peaks at one or more of the following 2θ angles: 7.4±0.2°, 11.9±0.2°, 17.7±0.2°, 20.5±0.2°, 21.5±0.2°, 24.0±0.2°; (3b) It has diffraction peaks at 6.8±0.2°, 7.4±0.2°, 8.9±0.2°, 19.3±0.2°, 19.7±0.2°, and 20.5±0.2°; (3c) It has diffraction peaks at 6.8±0.2°, 7.4±0.2°, 8.9±0.2°, 17.7±0.2°, 19.3±0.2°, 19.7±0.2°, 20.5±0.2°, and 24.0±0.2°; (3d) It has diffraction peaks at 6.8±0.2°, 7.4±0.2°, 8.9±0.2°, 11.9±0.2°, 17.7±0.2°, 19.3±0.2°, 19.7±0.2°, 20.5±0.2°, 21.5±0.2°, and 24.0±0.2°; (3e) The positions of its diffraction peaks are shown in Table 3: Table 3 ; Alternatively, the X-ray powder diffraction pattern of the second oxalate crystal form satisfies one or more of the following conditions: (4a) It has diffraction peaks at one or more of the following 2θ angles: 7.6±0.2°, 16.1±0.2°, 17.9±0.2°, 19.2±0.2°, 21.2±0.2°, 21.6±0.2°, 22.8±0.2°, 25.8±0.2°, 26.3±0.2°, 26.6±0.2°, 28.8±0.2°, 30.7±0.2°, 35.2±0.2°; (4b) It has diffraction peaks at 8.5±0.2°, 10.6±0.2°, 14.3±0.2°, 18.2±0.2°, 21.2±0.2°, 22.4±0.2°, and 26.6±0.2°; (4c) It has diffraction peaks at 8.5±0.2°, 10.6±0.2°, 14.3±0.2°, 17.9±0.2°, 18.2±0.2°, 21.2±0.2°, 22.4±0.2°, 22.8±0.2°, 25.8±0.2°, and 26.6±0.2°; (4d) It has diffraction peaks at 7.6±0.2°, 8.5±0.2°, 10.6±0.2°, 14.3±0.2°, 16.1±0.2°, 17.9±0.2°, 18.2±0.2°, 19.2±0.2°, 21.2±0.2°, 21.6±0.2°, 22.4±0.2°, 22.8±0.2°, 25.8±0.2°, 26.3±0.2°, 26.6±0.2°, 28.8±0.2°, 30.7±0.2°, and 35.2±0.2°; (4e) The positions of its diffraction peaks are shown in Table 4: Table 4 ; Alternatively, the X-ray powder diffraction pattern of the sodium salt crystal form satisfies one or more of the following conditions: (5a) It has diffraction peaks at one or more of the following 2θ angles: 12.4±0.2°, 13.6±0.2°, 15.0±0.2°, 16.7±0.2°, 16.9±0.2°, 24.1±0.2°, 27.1±0.2°; (5b) It has diffraction peaks at 4.9±0.2°, 9.7±0.2°, 15.0±0.2°, 16.7±0.2°, 17.6±0.2°, 18.7±0.2°, and 19.6±0.2°; (5c) It has diffraction peaks at 4.9±0.2°, 9.7±0.2°, 13.6±0.2°, 15.0±0.2°, 16.7±0.2°, 17.6±0.2°, 18.7±0.2°, 19.6±0.2°, and 24.1±0.2°; (5d) It has diffraction peaks at 4.9±0.2°, 9.7±0.2°, 12.4±0.2°, 13.6±0.2°, 15.0±0.2°, 16.7±0.2°, 16.9±0.2°, 17.6±0.2°, 18.7±0.2°, 19.6±0.2°, 24.1±0.2°, and 27.1±0.2°; (5e) The positions of its diffraction peaks are shown in Table 5: Table 5 ; Alternatively, the X-ray powder diffraction pattern of the potassium salt crystal form satisfies one or more of the following conditions: (6a) It has diffraction peaks at one or more of the following 2θ angles: 11.5±0.2°, 12.0±0.2°, 12.2±0.2°, 12.7±0.2°, 13.8±0.2°, 15.2±0.2°, 16.7±0.2°, 19.2±0.2°, 20.5±0.2°, 21.7±0.2°, 23.1±0.2°, 23.8±0.2°, 25.5±0.2°, 28.7±0.2°; (6b) It has diffraction peaks at 5.1±0.2°, 10.1±0.2°, 12.7±0.2°, 17.3±0.2°, 17.6±0.2°, 19.2±0.2°, 21.7±0.2°, 22.2±0.2°, and 28.7±0.2°; (6c) It has diffraction peaks at 5.1±0.2°, 10.1±0.2°, 12.0±0.2°, 12.7±0.2°, 13.8±0.2°, 17.3±0.2°, 17.6±0.2°, 19.2±0.2°, 21.7±0.2°, 22.2±0.2°, 23.8±0.2°, and 28.7±0.2°; (6d) It has diffraction peaks at 5.1±0.2°, 10.1±0.2°, 11.5±0.2°, 12.0±0.2°, 12.7±0.2°, 13.8±0.2°, 15.2±0.2°, 17.3±0.2°, 17.6±0.2°, 19.2±0.2°, 21.7±0.2°, 22.2±0.2°, 23.1±0.2°, 23.8±0.2°, 25.5±0.2°, and 28.7±0.2°; (6e) It has diffraction peaks at 5.1±0.2°, 10.1±0.2°, 11.5±0.2°, 12.0±0.2°, 12.2±0.2°, 12.7±0.2°, 13.8±0.2°, 15.2±0.2°, 16.7±0.2°, 17.3±0.2°, 17.6±0.2°, 19.2±0.2°, 20.5±0.2°, 21.7±0.2°, 22.2±0.2°, 23.1±0.2°, 23.8±0.2°, 25.5±0.2°, and 28.7±0.2°; (6f) The positions of its diffraction peaks are shown in Table 6: Table 6 。 7. The solid form of the compound of formula (I) according to claim 6, characterized in that, The first free state crystal form of the compound shown in Formula I is free state crystal form A, and the free state crystal form A satisfies one or more of the following conditions: (7a) Its X-ray powder diffraction pattern is shown in Figure 2; (7b) Its differential scanning spectroscopy analysis showed an endothermic peak at 154.5 ºC ± 3 ℃; (7c) Its thermogravimetric analysis chart shows a weight loss of 1.09±3% at 150℃±3℃; (7d) Its thermogravimetric analysis diagram / differential scanning calorimetry analysis diagram is shown in Figure 3; (7e) Its variable temperature X-ray powder diffraction pattern is shown in Figure 5; Alternatively, the second free state crystal form is free state crystal form B, and the free state crystal form B satisfies one or more of the following conditions: (8a) The X-ray powder diffraction patterns of the sample before and after drying are shown in Figure 6; (8b) Its differential scanning spectroscopy analysis showed an endothermic peak at 53.4 ºC ± 3 ℃; (8c) Its thermogravimetric analysis chart shows a weight loss of 4.32±3% at 150℃±3℃; (8d) Its thermogravimetric analysis diagram / differential scanning calorimetry analysis diagram is shown in Figure 7; (8e) The X-ray powder diffraction patterns before and after the heating experiment are shown in Figure 9; Alternatively, the first oxalate crystal form is oxalate crystal form A, and oxalate crystal form A satisfies one or more of the following conditions: (9a) Its X-ray powder diffraction pattern is shown in Figure 11; (9b) Its differential scanning spectroscopy analysis showed an endothermic peak at 88.6 ºC ± 3 ℃; (9c) Its thermogravimetric analysis chart shows a weight loss of 5.47±3% at 100℃±3℃; (9d) Its thermogravimetric analysis diagram / differential scanning calorimetry analysis diagram is shown in Figure 12; Alternatively, the second oxalate crystal form is oxalate crystal form B, which satisfies one or more of the following conditions: (10a) Its X-ray powder diffraction pattern is shown in Figure 14; (10b) Its differential scanning chromatogram shows an endothermic peak at 145.1 ºC ± 3 ℃; (10c) Its thermogravimetric analysis chart shows a weight loss of 1.33±3% at 120℃±3℃; (10d) Its thermogravimetric analysis diagram / differential scanning calorimetry analysis diagram is shown in Figure 15; Alternatively, the sodium salt crystal form is sodium salt crystal form A, and sodium salt crystal form A satisfies one or more of the following conditions: (11a) Its X-ray powder diffraction pattern is shown in Figure 17; (11b) Its differential scanning chromatogram shows an endothermic peak at 43.6 ± 3 °C and / or 87.9 ºC ± 3 °C; (11c) Its thermogravimetric analysis chart shows a weight loss of 9.04±3% at 100℃±3℃; (11d) Its thermogravimetric analysis diagram / differential scanning calorimetry analysis diagram is shown in Figure 18; Alternatively, the potassium salt crystal form is potassium salt crystal form A, and potassium salt crystal form A satisfies one or more of the following conditions: (12a) Its X-ray powder diffraction pattern is shown in Figure 20; (12b) Its differential scanning chromatogram shows an endothermic peak at 80.3 ± 3 °C and / or 144.9 ºC ± 3 °C; (12c) Its thermogravimetric analysis chart shows a weight loss of 7.41±3% at 100℃±3℃; (12d) Its thermogravimetric analysis diagram / differential scanning calorimetry analysis diagram is shown in Figure 21.
8. A method for preparing a compound in solid form as shown in formula (I), characterized in that, The crystal form of the compound shown in formula (I) is the first free state crystal form or the second free state crystal form as described in any one of claims 5, 6, and 7; The salt of the compound represented by formula (I) and the crystal form of the salt are the first oxalate crystal form, the second oxalate crystal form, the sodium salt crystal form or the potassium salt crystal form of the compound represented by formula (I) as described in any one of claims 3, 4, 6 or 7. The preparation method of the first free crystal form includes the following steps: dissolving the compound shown in formula (I) in a solvent and stirring at room temperature to obtain the first free crystal form; the solvent is H2O, an organic solvent, or a mixed solvent, preferably H2O, CHCl3, MIBK, MTBE, EtOAc, EtOH, MEK, IPAc, THF, Acetone, DCM, 1,4-Dioxane, MeOH, Anisole, 2-MeTHF, or ACN; the mixed solvent is a mixture of organic solvent and water, a mixture of organic solvent and n-Heptane, or a mixture of organic solvent and IPE; the mixed solvent is preferably a mixture of CHCl3 and n-Heptane, a mixture of EtOH and n-Heptane, or a mixture of EtOAc and n-Heptane. Alternatively, the preparation method of the first free crystal form includes the following steps: dissolving the compound shown in formula (I) in a solvent, adding a small amount of seed crystals to the system, and stirring at room temperature to obtain the first free crystal form; the solvent is H2O, an organic solvent, or a mixed solvent, preferably H2O, CHCl3, MIBK, MTBE, EtOAc, EtOH, MEK, IPAc, THF, Acetone, DCM, 1,4-Dioxane, MeOH, Anisole, 2-MeTHF, or ACN; the mixed solvent is a mixture of organic solvent and water, a mixture of organic solvent and n-Heptane, or a mixture of organic solvent and IPE; the mixed solvent is preferably a mixture of EtOH and n-Heptane. Alternatively, the preparation method of the second free crystal form includes the following steps: dissolving the compound shown in formula (I) in a solvent, then adding an antisolvent and allowing it to stand at room temperature to obtain the second free crystal form; the solvent is preferably 1,4-Dioxane or ACN; the antisolvent is preferably IPE, n-Pentane or H2O; Alternatively, the preparation method of the first oxalate crystal form includes the following steps: mixing the compound shown in formula (I), oxalic acid, and solvent, and slurrying at room temperature to obtain the first oxalate crystal form; wherein the solvent is a polar solvent; Alternatively, the preparation method of the second oxalate crystal form includes the following steps: mixing the compound shown in formula (I), oxalic acid, and solvent, and slurrying to obtain the second oxalate crystal form; wherein the solvent is a non-polar solvent; Alternatively, the method for preparing the sodium salt crystal form includes the following steps: mixing the compound shown in formula (I), sodium hydroxide, and solvent, and slurrying at room temperature to obtain the sodium salt crystal form; wherein the solvent is a non-polar solvent; Alternatively, the method for preparing the potassium salt crystal form includes the following steps: mixing the compound shown in formula (I), potassium hydroxide, and solvent, and slurrying at room temperature to obtain the potassium salt crystal form; the solvent is a non-polar solvent.
9. The preparation method according to claim 8, characterized in that, The preparation method of the first free crystal form satisfies one or more of the following conditions: (13a) In the preparation method of the first free crystal form, the compound shown in formula (I) is added to a mixed solvent, stirred at room temperature, the solid is separated by centrifugation, and the first free crystal form is obtained by vacuum drying at room temperature or 50°C. (13b) The mixed solvent can be added all at once or one solvent can be added first, followed by another solvent; (13c) The volume ratio of the mixed solvent is selected from (0.5-2):1; preferably 1:1; (13d) The mixed solvent is selected from CHCl3 / n-Heptane (1:1, V / V), EtOH / n-Heptane (0.5:1.5, V / V), and EtOAc / n-Heptane (1:1, V / V). (13e) The room temperature stirring time is selected from 0.5 days, 1 day, 2 days or 3 days; (13f) In the preparation method of the first free crystal form, the compound shown in formula (I) is added to EtOH to dissolve, a small amount of seed crystal of the first free crystal form is added to the clear solution, and then n-Heptane is slowly added in batches, stirred at room temperature, the solid is separated by centrifugation and vacuum dried at room temperature to obtain the first free crystal form; (13g) The volume ratio of EtOH to n-Heptane is selected from 1:(1-5); preferably 1:3; Alternatively, in the preparation method of the second free crystal form, the compound shown in formula (I) is dissolved in 1,4-Dioxane, H2O is added, and the solid is precipitated by standing at room temperature under a sealed condition. The solid is then dried under vacuum at room temperature to obtain the second free crystal form. Alternatively, in the method for preparing the first oxalate crystal form, the method for preparing the first oxalate crystal form satisfies one or more of the following conditions: (14a) The equivalent ratio of the compound shown in formula (I) to oxalic acid is (0.5-2):1; preferably 1:1; (14b) The mass-to-volume ratio of the compound shown in formula (I) to the solvent is 10-50 mg / mL; preferably 40 mg / mL; (14c) The polar solvent is selected from ACN; (14d) The room temperature pulping time is selected from 1-5 days; preferably 3 days; Alternatively, in the method for preparing the second oxalate crystal form, the method for preparing the second oxalate crystal form satisfies one or more of the following conditions: (15a) The equivalent ratio of the compound shown in formula (I) to oxalic acid is (0.5-2):1; preferably 1:1; (15b) The mass-to-volume ratio of the compound represented by formula (I) to the solvent is 10-50 mg / mL; preferably 40 mg / mL; (15c) The nonpolar solvent is selected from EtOAc or MIBK; (15d) The pulping time is selected from 1-5 days; preferably 3 days; Alternatively, in the method for preparing the sodium salt crystal form, the compound shown in formula (I), 1 equivalent of NaOH and MIBK are pulped at room temperature for 1-3 days, the solid is separated by centrifugation and vacuum dried at 50°C to obtain the sodium salt crystal form; the pulping time is preferably 2 days; Alternatively, in the method for preparing the potassium salt crystal form, the compound shown in formula (I), 1 equivalent of KOH and MIBK are pulped at room temperature for 1-3 days, the solid is separated by centrifugation and vacuum dried at 50°C to obtain the potassium salt crystal form; the pulping time is preferably 2 days.
10. A pharmaceutical composition, characterized in that, The compound comprising any one of claims 1 to 9 as described in formula (I) is in solid form, and optionally further comprises at least one pharmaceutical excipient.
11. Use of the solid form of the compound of any one of claims 1 to 7 as of formula (I) or the pharmaceutical composition of claim 10 in the preparation of a medicament for the prevention and / or treatment of AT2R-mediated diseases; And / or, to prevent and / or treat diseases for which a reduction in Ang II action is desired or required; And / or, to prepare a drug, pharmaceutical composition or formulation as an AT2R antagonist.
12. The use according to claim 11, characterized in that, The disease is described as neuropathy or neuropathic pain.
13. The use according to claim 12, characterized in that, The disease in question is postherpetic neuralgia or diabetic peripheral neuropathy.
Citation Information
Patent Citations
AT2R antagonist and application thereof
CN119798233A
Compounds for the treatment of pain, in particular neuropathic pain, and / or other diseases or disorders that are associated with at2r and / or at2r mediated signaling
WO2023006893A1